Biaxially oriented polyolefin film

By blending the cyclic olefin resin into the polypropylene resin and performing biaxial stretching and heat treatment, the biaxially oriented polyolefin film is solved, and the film is efficient, economical and environmentally friendly performance improvement is achieved.

CN119654369APending Publication Date: 2025-03-18TORAY INDUSTRIES INC
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202380057599.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-26
Filing Date
2023-09-22
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The existing biaxially oriented polyolefin films are prone to deform under high temperature environments, and in their application in optical components, the phase difference is insufficient, making it difficult to take into account both the inspection adaptability and high temperature processability.

Method used

By blending a cyclic olefin resin into a polypropylene resin and using biaxial stretching and heat treatment processes, a biaxially oriented polyolefin film with excellent optical characteristics and heat resistance was prepared.

Benefits of technology

The stability of maintaining film performance at high temperatures is achieved, the inspection adaptability and optical characteristics of the film are enhanced, the cost is reduced, and the transparency and mechanical strength of the film are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119654369A_ABST
    Figure CN119654369A_ABST
Patent Text Reader

Abstract

A biaxially oriented polyolefin film in which the value obtained by dividing the phase difference (Rth (nm)) in the thickness direction by the film thickness ([mu] m) is 1.0-16.0 inclusive, and the thermal shrinkage rate in the main orientation direction at 150 DEG C is-5.0%-6.0% inclusive. The present invention addresses the problem of providing a biaxially oriented polyolefin film which, when used as a film for industrial materials, has both adaptability to inspection of a target member and processability at high temperatures.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a biaxially oriented polyolefin film which can achieve both inspection suitability for a target member and processability at high temperatures when used as an industrial material film. Background Art

[0002] Biaxially oriented polyolefin films, especially biaxially oriented polypropylene films, are suitable for use as protective films, process films, and industrial material films such as release films due to their excellent surface release properties. Among them, the low hygroscopicity derived from polyolefins is used as a protective film for optical components such as polarizing plates. When the biaxially oriented polyolefin film is applied to these optical components, the phase difference in the thickness direction of the film is required to be low in order to suppress the generation of interference colors and rainbow colors. Furthermore, in order to prevent dimensional changes even in high temperature environments, high heat resistance is also required.

[0003] Therefore, in optical component applications that require low phase difference and heat resistance at a high level, films formed from cyclic olefin resins with a high glass transition temperature are used. However, there are problems such as high cost due to the high price of the raw materials of the resin, poor operability due to the fact that it is an unstretched film and is not easy to be thinned, and research has been conducted on whether it is possible to use cheap polypropylene resins instead.

[0004] However, polypropylene resin has a low melting point and glass transition temperature, so the shrinkage and deformation of the film in a high temperature environment become large, and the use temperature range is limited. In addition, the phase difference is often insufficient for the above-mentioned applications.

[0005] As means for solving the above-mentioned problems, films in which cyclic olefin resins are blended into polypropylene resins (e.g., Patent Documents 1 and 2), films in which polypropylene resins are laminated on both sides of a layer formed of a cyclic olefin resin (e.g., Patent Document 3), etc. have been proposed, which achieve a balance between heat resistance and cost by reducing the amount of expensive cyclic olefin resins used.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: Japanese Patent Application Laid-Open No. 9-272188

[0009] Patent Document 2: Japanese Patent Application No. 2020-521867

[0010] Patent Document 3: Japanese Patent Application Publication No. 2018-034510 Summary of the invention

[0011] Problems to be solved by the invention

[0012] However, although the films of patent documents 1 and 2 improve heat resistance by blending cyclic olefin resin with polypropylene resin, the dispersion of the structural domain of cyclic olefin resin is insufficient, and it is difficult to make the quality of the film uniform. Therefore, when used as industrial material films such as protective films, process films, and release films, there is a problem of insufficient inspection adaptability of the object component that is bonded to the film, and this problem is particularly significant when the object component is an optical component such as a polarizing plate. In addition, the film of patent document 3 is a film in which cyclic olefin resin is laminated on the inner layer and polypropylene resin is laminated on the surface layer. When used in a process where high tension is applied, there is a problem of undesirable conditions such as peeling occurring at the laminate interface. Therefore, the subject of the present invention is to solve the above problems. That is, a biaxially oriented polyolefin film having both inspection adaptability of the object component and processability at high temperature is provided when used as an industrial material film.

[0013] Means for solving problems

[0014] In order to solve the above-mentioned problems, the biaxially oriented polyolefin film of the present invention comprises the following constitution. That is, the biaxially oriented polyolefin film of the present invention is a biaxially oriented polyolefin film, the value obtained by dividing the phase difference Rth (nm) in the thickness direction by the film thickness (μm) is 1.0 or more and 16.0 or less, the heat shrinkage rate in the main orientation direction at 150°C is -5.0% or more and 6.0% or less, and contains a cyclic olefin resin.

[0015] Effects of the Invention

[0016] The present invention can provide a biaxially oriented polyolefin film that has both inspection suitability for target components and processability at high temperatures when used as an industrial material film such as a protective film, a process film, and a release film. The biaxially oriented polyolefin film of the present invention can be particularly suitable for use as an industrial material film for optical purposes due to the above characteristics. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is a schematic diagram showing a cross section (cross section X) in the thickness direction orthogonal to the main orientation direction of a biaxially oriented polyolefin film according to one embodiment of the present invention.

[0018] Figure 2 For Figure 1 In the scheme, a graph is plotted along a 1 μm line segment (symbol 4) parallel to the thickness direction, with the white portion set to 0 and the black portion set to 1, relative to the length in the thickness direction.

[0019] Figure 3 To express and Figure 1 A schematic diagram of a cross section (cross section X) in the thickness direction orthogonal to the main orientation direction of a biaxially oriented polyolefin film according to another embodiment of the present invention. DETAILED DESCRIPTION

[0020] The biaxially oriented polyolefin film of the present invention is a biaxially oriented polyolefin film having a value obtained by dividing the phase difference Rth (nm) in the thickness direction by the film thickness (μm) of 1.0 or more and 16.0 or less, a heat shrinkage rate in the main orientation direction at 150°C of -5.0% or more and 6.0% or less, and containing a cyclic olefin resin. The biaxially oriented polyolefin film of the present invention is specifically described below.

[0021] Hereinafter, the biaxially oriented polyolefin film is sometimes referred to as simply a film. It should be noted that the biaxially oriented polyolefin film of the present invention does not have a plurality of pores because it is not a microporous film. That is, in the present invention, the so-called biaxially oriented polyolefin film refers to a biaxially oriented polyolefin film other than a microporous film. The so-called microporous film here is defined as a film having the following pore structure, wherein the pore structure penetrates both surfaces of the film, and has an air permeability of less than 5,000 seconds / 100mL at 23°C and a relative humidity of 65% in terms of the permeation time of 100ml of air using a B-type Gurley tester of JIS P 8117 (1998). In addition, the so-called biaxial orientation refers to the orientation of molecules along two directions orthogonal to the film surface, which can be achieved by stretching an unstretched sheet along two directions orthogonal to the film surface to form a film.

[0022] So-called polyolefin film refers to a film comprising a polyolefin resin of more than 50% by mass and less than 100% by mass when all the components constituting the film are set to 100% by mass. When all the components constituting the film are set to 100% by mass, the content of the polyolefin resin in the polyolefin film is preferably more than 70% by mass and less than 100% by mass, more preferably more than 90% by mass and less than 100% by mass, further preferably more than 95% by mass and less than 100% by mass, particularly preferably more than 96% by mass and less than 100% by mass, most preferably more than 97% by mass and less than 100% by mass. It should be noted that, in the case of comprising a plurality of components equivalent to polyolefin resins, as long as these components are added together to exceed 50% by mass and be less than 100% by mass, it is equivalent to polyolefin film.

[0023] The so-called polyolefin resin refers to a resin containing more than 50 mol% and less than 100 mol% of olefin units when all the structural units constituting the resin are set to 100 mol%. The so-called polypropylene resin refers to a resin containing more than 50 mol% and less than 100 mol% of propylene units when all the structural units constituting the resin are set to 100 mol%, and does not meet the following definition of cyclic olefin resins.

[0024] The so-called cyclic olefin resin refers to a polyolefin resin containing 10 mol% or more and 100 mol% or less of cyclic olefin units when all structural units constituting the resin are set to 100 mol%. It should be noted that, for a resin containing multiple structural units equivalent to cyclic olefin units, even if the individual cyclic olefin units are less than 10 mol%, as long as the total of these structural units exceeds 10 mol%, it is equivalent to a cyclic olefin resin.

[0025] From the viewpoint of suppressing interference color and rainbow color unevenness and improving heat resistance, it is important that the biaxially oriented polyolefin film of the present invention contains cyclic olefin resin. By adopting such a scheme, the optical properties and heat resistance of the obtained biaxially oriented polyolefin film are excellent due to the low birefringence and high heat resistance of the cyclic olefin resin. Regarding the cyclic olefin resin, the cyclic olefin structure of the side chain becomes a perpendicular polarizability ellipsoid relative to the polymer main chain, and the polarizability anisotropy is low due to this structure, resulting in low birefringence.

[0026] From the viewpoint of obtaining excellent optical properties and heat resistance, when the total resin components of the biaxially oriented polyolefin film are set to 100% by mass, the content of the cyclic olefin resin in the biaxially oriented polyolefin film of the present invention is preferably 2.0% by mass or more, more preferably 5.0% by mass or more, further preferably 7.5% by mass or more, and particularly preferably 9.0% by mass or more. On the other hand, from the viewpoint of ease of stretching and mechanical strength, the content of the cyclic olefin resin is preferably less than 50% by mass, more preferably 40% by mass or less, further preferably 30% by mass or less, particularly preferably 20% by mass or less, and most preferably 15% by mass or less.

[0027] From the viewpoint of suppressing interference color, rainbow color unevenness, and improving the inspection adaptability of the object member when used as an industrial material film, the phase difference Rth (nm) in the thickness direction of the biaxially oriented polyolefin film of the present invention divided by the film thickness (μm) is 1.0 or more and 16.0 or less. Here, the so-called object member refers to the member that is bonded to the biaxially oriented polyolefin film of the present invention when the biaxially oriented polyolefin film of the present invention is used as an industrial material film such as a protective film, a process film, and a release film. For example, when the biaxially oriented polyolefin film is used as a polarizing plate protective film, the polarizing plate becomes the object member. In the case of using the biaxially oriented polyolefin film as an industrial material film, it is required that even if the biaxially oriented polyolefin film is bonded to the object member, the necessary characteristics can be suppressed as much as possible. Regarding this characteristic, when the object member is a member for optical purposes (hereinafter, sometimes referred to as an optical member.), it is difficult to achieve because the inspection item is an inspection item that requires precision such as optical characteristics (such as phase difference characteristics, etc.). It should be noted that the so-called thickness direction refers to the direction perpendicular to the film surface, and the phase difference Rth in the thickness direction can be calculated from the refractive index with respect to light of wavelength 590nm measured by a known Abbe refractometer (the detailed measurement method is described later).

[0028] In such a case, if the value obtained by dividing the phase difference Rth (nm) in the thickness direction of the biaxially oriented polyolefin film by the film thickness (μm) is less than 16.0, the phase difference characteristics of the polarizing plate can be inspected even in the state where the biaxially oriented polyolefin film is bonded as a protective film in the inspection process before the polarizing plate is shipped out, which is advantageous in terms of cost and quality maintenance.

[0029] The phase difference Rth in the thickness direction is a parameter that increases in proportion to the film thickness, and can usually be reduced by thinning the film. However, if the film is thinned, the following problems arise: stiffness decreases and operability deteriorates; planarity tends to deteriorate due to use in a high temperature environment, so it is important to reduce the phase difference while maintaining the film thickness to a certain extent in the present invention. That is, in the biaxially oriented polyolefin film of the present invention, in order to eliminate the influence of the film thickness on the phase difference Rth in the thickness direction, it is important to make the value obtained by dividing the phase difference Rth in the thickness direction by the film thickness low.

[0030] From the viewpoint of suppressing interference color and rainbow color unevenness and improving the inspection suitability of the target member (especially optical member), the upper limit of the value obtained by dividing the Rth (nm) of the biaxially oriented polyolefin film by the film thickness (μm) is preferably 15.0, more preferably 14.0, further preferably 12.0, and particularly preferably 11.0. From the above viewpoint, the lower the value obtained by dividing the Rth (nm) of the biaxially oriented polyolefin film by the film thickness (μm), the more preferred, but if the feasibility is taken into consideration, 1.0 is substantially the lower limit.

[0031] As a method for controlling the value obtained by dividing Rth (nm) by the film thickness (μm) within the above range, for example, a method of preparing a film containing a polypropylene resin and a cyclic olefin resin with low birefringence can be cited. Generally speaking, the cyclic olefin structure of the side chain of the cyclic olefin resin forms a perpendicular polarizability ellipsoid relative to the polymer main chain. The cyclic olefin resin has a low polarizability anisotropy due to this structure and has a low birefringence. Therefore, the more the content of the cyclic olefin resin in the film, the lower the value obtained by dividing Rth by the film.

[0032] On the other hand, if the content of the cyclic olefin resin in the film increases, the tensile property deteriorates and becomes disadvantageous in terms of mechanical strength, and the manufacturing cost also increases. In addition, it is known that resins with different crystallinity such as polypropylene resin and cyclic olefin resin are difficult to be compatible with each other, so when the two resins are blended, a sea island structure in which a domain formed by another resin exists in a matrix formed by one resin is formed. In the case where the polypropylene resin and the cyclic olefin resin are simply blended, sometimes a gap is generated at the interface of the domain, thereby damaging transparency and appearance, and sometimes stress is concentrated in the gap due to the application of strong tension, thereby breaking the film.

[0033] In order to overcome these problems, the characteristics required for improving the inspection adaptability of the target member (especially optical member) and the processability at high temperature, such as transparency and operability, are improved, and the value obtained by dividing the Rth (nm) in the thickness direction by the film thickness (μm) is controlled within the above range. For example, the following measures are effective: selecting a cyclic olefin resin having a refractive index in the range described below; preparing a composite resin raw material obtained by pre-mixing the cyclic olefin resin and the polypropylene resin to pre-microdisperse the structural domain of the cyclic olefin resin; making the amount of the cyclic olefin resin in the biaxially oriented polypropylene film within the above range; etc. In addition, when the film is melt-extruded, the melting temperature in the extruder, the short tube temperature from the filter to the die, and the die lip temperature are gradually lowered, so that the structural domain is elongated along the extrusion direction and the thickness of the structural domain is thin. In addition, it is also effective to expand the stretching interval of longitudinal stretching, heat the film from both sides of the stretching film with a radiation heater, and neck it, so as to elongate the structural domain slenderly along the stretching direction and make the thickness of the structural domain thin. It should be noted that these methods do not require only one to be used, and can also be used in appropriate combinations (this is also the case in the following means for realizing each characteristic in the present invention.).

[0034] From the viewpoint of improving the adaptability to the processing steps under high temperature environment, the heat shrinkage rate of the main orientation direction of the biaxially oriented polyolefin film of the present invention at 150°C is -5.0% or more and 6.0% or less. Not limited to the protection use of the above-mentioned polarizing plate, when the biaxially oriented polyolefin film is used as a protective film or a process film, it is sometimes exposed to a high temperature environment, and further exposed to a high temperature and high tension environment. Therefore, the biaxially oriented polyolefin film is required to maintain performance under these environments.

[0035] In such a case, by making the heat shrinkage rate of the biaxially oriented polyolefin film in the main orientation direction at 150°C 6.0% or less, even when the film is attached to an adherend and transported in a roll-to-roll process under high-temperature conditions such as an oven, the deterioration of planarity caused by the generation of wrinkles due to heating can be suppressed, and the film can be used in a wide range of temperature environments. From the above viewpoints, the upper limit of the heat shrinkage rate in the main orientation direction at 150°C is preferably 4.0%, more preferably 3.0%, further preferably 2.0%, and most preferably 1.0%.

[0036] On the other hand, if the heat shrinkage in the main orientation direction at 150°C is less than 0%, it means that the biaxially oriented polyolefin film expands in the main orientation direction by heating. If the heat shrinkage in the main orientation direction at 150°C is less than -5.0%, the planarity of the roll may deteriorate when the roll is stored as a film. From the above viewpoints, the lower limit of the heat shrinkage in the main orientation direction at 150°C is preferably -4.0%, more preferably -3.0%, and further preferably -2.0%.

[0037] In order to control the heat shrinkage rate in the main orientation direction at 150°C to the above range, for example, it is effective to set the glass transition temperature of the cyclic olefin resin to the preferred range described below, use a polypropylene resin with high crystallinity and a high meso pentad fraction, and stabilize the molecular chains that are insufficiently oriented after longitudinal stretching by adjusting the preheating temperature and the stretching temperature during transverse stretching to the range described below so as to make the preheating temperature higher than the stretching temperature.

[0038] The so-called main orientation direction here refers to the direction showing the highest value when the Young's modulus is measured in each direction with an angle of 0° to 175° at 5° intervals relative to the arbitrary direction in the film surface, and the so-called main orientation orthogonal direction refers to the direction orthogonal to the main orientation direction in the film surface. The so-called Young's modulus here refers to the Young's modulus calculated by placing a rectangular sample of 150 mm in length (measurement direction) × 10 mm in width at an initial chuck distance of 50 mm, and performing a tensile test at room temperature at a tensile speed of 300 mm / min according to the method specified in JIS K7161 (2014). It should be noted that the details of the determination method of Young's modulus are described later.

[0039] However, in the case where the Young's modulus cannot be measured and calculated by the above method because a sample of the above size cannot be obtained, the crystal orientation of the polypropylene α crystal (110) plane of the biaxially oriented polyolefin film is measured by wide-angle X-ray as follows, and the main orientation direction is set based on the following judgment criteria. That is, X-rays (CuKα rays) are made incident in a direction perpendicular to the film surface, and the crystal peak in 2θ=about 14° (α crystal (110) plane) is scanned in the circumferential direction, and the direction with the highest diffraction intensity in the obtained diffraction intensity distribution is set as the main orientation direction, and the direction orthogonal to it is set as the main orientation orthogonal direction.

[0040] In addition, in the present invention, the direction parallel to the direction of film-forming biaxially oriented polyolefin film is referred to as the length direction, film-forming direction or MD direction, and the direction orthogonal to the length direction in the film plane is referred to as the width direction or TD direction. If the biaxially oriented polyolefin film is obtained by stretching in the length direction and the width direction, usually, one of the stretching directions becomes the main orientation direction, and the other becomes the orthogonal direction to the main orientation.

[0041] The heat shrinkage rate in the main orientation direction at 150°C can be measured by the following method and steps. First, a sample is cut out with the main orientation direction and the main orientation orthogonal direction of the biaxially oriented polyolefin film as each side having a square size of 10 cm to obtain a sample. Then, the obtained sample is sandwiched on both sides with a paper of 0.09 mm thickness and heated at 150°C for 15 minutes. After the heating is completed, the change rate of the dimension of the film in the main orientation orthogonal direction before and after heating is measured and set as the heat shrinkage rate in each direction. It should be noted that the detailed measurement method is described later.

[0042] From the viewpoint of improving heat resistance, the biaxially oriented polyolefin film of the present invention preferably has a tanδ of 0.01 or more and 0.23 or less at 150°C in the main orientation direction and the direction orthogonal to the main orientation. Tanδ is also called loss tangent, which is related to the degree of mobility of the molecular chains in the film. The lower the tanδ, the lower the molecular mobility and the more thermally stable it is. From the above viewpoints, tanδ at 150°C is preferably low, with an upper limit of more preferably 0.20, further preferably 0.18, and most preferably 0.16. The lower the tanδ at 150°C, the more preferred, but substantially 0.01 is the lower limit. It should be noted that tanδ can be measured by a dynamic viscoelasticity method, which will be described in detail later.

[0043] In order to control tanδ at 150°C within the above range in the main orientation direction and the direction orthogonal to the main orientation, for example, the following measures are effective: setting the glass transition temperature of the cyclic olefin resin to the preferred range described below; using a polypropylene resin with high crystallinity (high mesogenic pentad fraction); expanding the stretching range of the longitudinal stretching, heating the film from both sides of the stretching film with a radiation heater while necking it, thereby uniformly orienting the molecular chains in the film; adjusting the preheating temperature and stretching temperature during transverse stretching to the range described below and making the preheating temperature higher than the stretching temperature to stabilize the molecular chains that are not fully oriented after the longitudinal stretching; etc.

[0044] From the viewpoint of improving mechanical strength and visibility, the biaxially oriented polyolefin film of the present invention preferably has a refractive index of more than 1.498 and less than 1.550 in the direction of the main orientation orthogonal direction. The refractive index is related to the degree of orientation of the molecular chain in the film. The greater the refractive index in the direction of the main orientation orthogonal direction, the greater the orientation of the molecular chain in the same direction, and the higher the mechanical strength in the same direction. From the above viewpoint, the refractive index in the direction of the main orientation orthogonal direction is preferably high, and the lower limit is more preferably 1.505, further preferably 1.510, particularly preferably 1.512, and most preferably 1.515. It should be noted that the so-called refractive index here is the refractive index when measured with sodium D rays (wavelength 589nm) as the light source, and its detailed determination method is described later.

[0045] By making the refractive index in the direction perpendicular to the main orientation 1.498 or more and 1.550 or less, or the above preferred range, the mechanical strength of the biaxially oriented polyolefin film in the direction perpendicular to the main orientation is improved. Therefore, by adopting such a scheme, even when the polyolefin film is used as a process film or a release film, high tension is applied in the same direction, and deformation or breakage of the polyolefin film can be reduced.

[0046] In order to make the refractive index in the direction perpendicular to the main orientation be 1.498 or more and 1.550 or less, for example, a method of adjusting the mixing conditions of the raw materials, the composition of the polyolefin film, and the method of making the film-making conditions within the range described below can be used in appropriate combination. In particular, it is effective to use a composite resin raw material obtained by pre-mixing a cyclic olefin resin and a polypropylene resin, to make the content of the cyclic olefin resin in the film within the above range (wherein, in the case of a single-layer structure of the biaxially oriented polyolefin film, the amount of the cyclic olefin resin in the entire biaxially oriented polyolefin film is made to be 25% by mass or less), and to perform high-multiple stretching in the longitudinal direction.

[0047] From the viewpoint of improving the optical properties, the biaxially oriented polyolefin film of the present invention preferably has a phase difference Re (nm) in the in-plane direction divided by the film thickness (μm) of 0.1 or more and 20.0 or less. From the above viewpoint, the value obtained by dividing the phase difference Re (nm) in the in-plane direction by the film thickness (μm) is preferably 19.0 or less, more preferably 17.0 or less, further preferably 14.0 or less, and particularly preferably 11.0 or less. The smaller the value obtained by dividing the Re (nm) in the in-plane direction by the film thickness (μm), the more preferred it is, and from the viewpoint of feasibility, the lower limit is 0.1. It should be noted that the so-called phase difference Re in the in-plane direction here refers to the phase difference in the in-plane direction at a wavelength of 590nm, and its detailed measurement method is described later.

[0048] By making the value obtained by dividing the Re (nm) in the in-plane direction by the film thickness (μm) be greater than 0.1 and less than 20.0 or within the above-mentioned preferred range, when a biaxially oriented polyolefin film is used as a protective film for optical components such as polarizing plates, the occurrence of interference colors and rainbow color unevenness caused by the birefringence of the biaxially oriented polyolefin film can be reduced, thereby improving the quality.

[0049] In order to make the phase difference Re (nm) in the in-plane direction divided by the film thickness (μm) to be greater than 0.1 and less than 20.0, for example, the mixing conditions of the raw materials, the composition of the polyolefin film, and the method of making the film-making conditions to be in the range described later can be appropriately combined and used. In particular, it is effective to use a composite resin raw material obtained by pre-mixing a cyclic olefin resin and a polypropylene resin, to make the content of the cyclic olefin resin in the film to be in the above range, and to stretch more isotropically on the basis of making the stretching ratio in the length direction and the width direction to be in the range described later. In addition, it is also effective to perform simultaneous biaxial stretching. It should be noted that the so-called "stretching more isotropically" here refers to stretching in two directions so that the ratio of the stretching ratio in the length direction and the width direction is closer to 1.

[0050] From the viewpoint of improving quality and visibility, the biaxially oriented polyolefin film of the present invention preferably has a kinetic friction coefficient μd in the orthogonal direction of the main orientation of 0.10 or more and 0.70 or less. From the above viewpoint, the kinetic friction coefficient μd in the orthogonal direction of the main orientation is more preferably 0.60 or less, further preferably 0.50 or less, particularly preferably 0.45 or less, and most preferably 0.40 or less. The kinetic friction coefficient μd in the orthogonal direction of the main orientation is preferably low, but substantially 0.10 is the lower limit. It should be noted that the kinetic friction coefficient μd in the orthogonal direction of the main orientation can be measured in accordance with JIS K 7125 (1999) after overlapping the orthogonal directions of the main orientation and the different faces of the film are in contact with each other. The detailed measurement method is described later.

[0051] By setting the dynamic friction coefficient μd in the direction perpendicular to the main orientation to 0.10 or more and 0.70 or less, when a polyolefin film is used as a protective film, wrinkles are less likely to be introduced when the film is transported together with an adherend, and winding displacement when winding together with an adherend is also reduced.

[0052] In order to make the dynamic friction coefficient μd in the direction orthogonal to the main orientation greater than or equal to 0.10 and less than or equal to 0.70, for example, the method of adjusting the layer structure and composition of the polyolefin film and the method of making the film-making conditions within the range described below can be appropriately combined and used. In particular, it is effective to form fine protrusions on the surface by making the biaxially oriented polyolefin film a laminated structure, and the surface layer contains olefin resins such as cyclic olefin resins, olefin elastomer resins, branched polypropylene resins, or poly-4-methylpentene-1 resins to a degree that does not become its main component. In addition, in the case where the biaxially oriented polyolefin film is a single-layer structure, it is effective to make the biaxially oriented polyolefin film itself the above-mentioned scheme instead of the surface layer in the case of the laminated structure. It is speculated that such surface protrusions are because: an alloy structure is formed by containing a small amount of the above-mentioned resins other than the branched polypropylene resin; the branched polypropylene resin acts as a crystal nucleating agent. In addition, a method of forming fine protrusions on the surface by making the temperature of the casting drum within the range described below can be used, and it can also be combined with the above-mentioned method.

[0053] From the viewpoint of suppressing the breakage of the film when foreign matter is mixed in when laminating with the adherend, the biaxially oriented polyolefin film of the present invention preferably has a product of puncture strength and thickness of 200 gf·μm or more and 5000 gf·μm or less. From the above viewpoint, the lower limit of the product of puncture strength and thickness is more preferably 500 gf·μm, more preferably 1000 gf·μm, more preferably 1500 gf·μm, and most preferably 1800 gf·μm. From the above viewpoint, the larger the upper limit of the product of puncture strength and thickness, the more preferred, and there is no particular restriction, but from the viewpoint of feasibility, it is preferably 5000 gf·μm, and more preferably 3000 gf·μm.

[0054] By making the product of the puncture strength and the thickness greater than or equal to 200 gf·μm and less than or equal to 5000 gf·μm, the risk of film breakage can be reduced even when the polyolefin film is used as the protective film and the film is laminated to an adherend having a sharply uneven surface. It should be noted that the puncture strength can be calculated as the puncture strength (g / μm) by puncturing a needle with a front end R of 1 mm at a speed of 2 mm / sec, reading the load when the needle penetrates, and dividing the value by the film thickness. The detailed measurement method is described later.

[0055] In order to make the product of the puncture strength and the thickness in the direction orthogonal to the main orientation axis be 200 gf·μm or more and 5000 gf·μm or less, for example, the kneading conditions of the raw materials, the composition of the polyolefin film, the method of making the film-making conditions within the range described below, etc. can be appropriately combined and used. In particular, the following measures are effective: using a composite resin raw material obtained by pre-mixing a cyclic olefin resin and a polypropylene resin; reducing the temperature of the casting drum within the range described below to make the spherulites of the unstretched polyolefin film small; making the content of the cyclic olefin resin in the film within the above range; expanding the stretching range of longitudinal stretching, heating the film from both sides of the stretching film with a radiation heater while necking it so that the molecular chains in the film are uniformly oriented; adjusting the preheating temperature and the stretching temperature during transverse stretching to the range described below so that the preheating temperature is higher than the stretching temperature so that the molecular chains that are not sufficiently oriented after longitudinal stretching are stabilized and uniformly stretched. In addition, the product of the puncture strength and the thickness can also be adjusted by adjusting the thickness.

[0056] The thickness of the biaxially oriented polyolefin film of the present invention is appropriately adjusted according to the purpose, and is not particularly limited. It is preferably 0.5 μm or more and 100 μm or less from the viewpoint of operability. The upper limit of the thickness is more preferably 60.0 μm, and more preferably 30.0 μm. The lower limit is more preferably 2.0 μm, more preferably 5.0 μm, and particularly preferably 10.0 μm. The thickness of the biaxially oriented polyolefin film can be adjusted by the screw speed of the extruder, the width of the unstretched sheet, the film-making speed, the stretching ratio, etc. within the range that does not reduce other physical properties. It should be noted that the thickness of the biaxially oriented polyolefin film can be measured with a known thickness micrometer, which is described in detail later.

[0057] The biaxially oriented polyolefin film of the present invention preferably has a position where the number of interfaces per 1 μm in the thickness direction is 3 or more and 1000 or less in the cross section (hereinafter sometimes referred to as cross section X) in the main orientation orthogonal direction. Here, the so-called thickness direction refers to the direction perpendicular to the film surface. The number of interfaces per 1 μm in the thickness direction is more preferably 5 or more, further preferably 7 or more, and most preferably 10 or more. The upper limit is not particularly limited, but is substantially 1000, preferably 50, and more preferably 30.

[0058] The method for determining the number of interfaces is described in detail later. The number of interfaces can be determined by the following steps. First, an ultrathin section of a biaxially oriented polyolefin film produced by a sectioning method is stained with RuO4, and the section X is observed by a transmission electron microscope (TEM). Then, the obtained observed image is binarized to determine the number of interfaces per 1 μm thickness in the section X. Figures 1 to 3, a description will be given of a configuration in which there is a position in the cross section X where the number of interfaces per 1 μm in the thickness direction is 3 or more and 1000 or less.

[0059] Figure 1 This is a schematic diagram showing a cross section X of a biaxially oriented polyolefin film according to one embodiment of the present invention. Figure 1 Symbols 1 to 4 in the figure respectively represent a part of the cross section X, a white part (a relatively weakly dyed part), a black part (a relatively strongly dyed part), and a line segment of 1 μm in length parallel to the thickness direction. The left figure is a part of the cross section X, and the right figure is an enlarged view of the periphery of the 1 μm line segment (symbol 4) parallel to the thickness direction. It should be noted that in the biaxially oriented polyolefin film of the present invention, the white part (non-dyed part) is a polypropylene resin, and the black part (dyed part) is a cyclic olefin resin.

[0060] Figure 2 For along Figure 1 The 1 μm line segment (symbol 4) parallel to the thickness direction in the scheme is plotted with respect to the length in the thickness direction, with the white portion set to 0 and the black portion set to 1. Figure 2 In the figure, the sum of the number of times the value switches from 0 to 1 and the number of times the value switches from 1 to 0 is defined as the number of interfaces per 1 μm in the thickness direction. Figure 2 In the example of , since the number of switching from 0 to 1 is 5 times and the number of switching from 1 to 0 is 5 times, the number of interfaces per 1 μm in the thickness direction in the cross section X is 10.

[0061] Figure 3 To illustrate an embodiment of the present invention (with Figure 1 ) is a schematic diagram of a cross section X of a biaxially oriented polyolefin film. Figure 3 Symbols 1 to 4 in the figure respectively represent a part of the cross section X, a white part (non-dyed part), a black part (dyed part), and a line segment of 1 μm in length parallel to the thickness direction. The left figure is a part of the cross section X, and the right figure is an enlarged view of the periphery of the 1 μm line segment (symbol 4) parallel to the thickness direction. Figure 3 In the case of the scheme, the number of interfaces per 1 μm in the thickness direction can also be determined by the same method as above.

[0062] By having a position where the number of interfaces per 1 μm in the thickness direction is 3 or more, the low birefringence and high heat resistance of the cyclic olefin resin can be reflected in the polyolefin film while maintaining the transparency of the biaxially oriented polyolefin film. When such a biaxially oriented polyolefin film is used as a protective film for optical components such as polarizing plates, the generation of interference colors and rainbow color unevenness caused by the birefringence of the biaxially oriented polyolefin film can be reduced, and the warping and wrinkling caused by shrinkage and expansion can be reduced, and as a result, the quality can be improved.

[0063] In the biaxially oriented polyolefin film of the present invention, as a method for forming a solution in which the number of interfaces per 1 μm in the thickness direction is more than 3 and less than 1000 in the cross section orthogonal to the main orientation direction-thickness direction, for example, the mixing conditions of the raw materials, the layer structure of the polyolefin film, the composition method, the method of making the film-making conditions to be the range described later, etc. can be appropriately combined and used. In particular, it is effective to improve the dispersibility of the cyclic olefin resin domain by using a composite resin raw material obtained by pre-mixing a cyclic olefin resin with a polypropylene resin and making the content of the cyclic olefin resin in the film to be the above range. In terms of film-making process, in particular, it is effective to make the thickness of the cyclic olefin resin domain thin by high-multiple stretching in the length direction and the width direction. In addition, a method can be used in which the number of layers of the film is made to be the range described later, so that the number of layers is large and the thickness of each cyclic olefin resin layer is thin.

[0064] The layer composition of the biaxially oriented polyolefin film of the present invention is as described above, as long as the biaxially oriented polyolefin film contains cyclic olefin resin, there is no particular restriction, and it can be a single film composition consisting of only a layer containing cyclic olefin resin (hereinafter sometimes referred to as A layer.), a layered composition consisting of a total of more than 2 layers of layers containing cyclic olefin resins in the thickness direction, and a layered composition consisting of a total of more than 2 layers of layers containing cyclic olefin resins and layers other than cyclic olefin resins in the thickness direction. In addition, in the case where the biaxially oriented polyolefin film of the present invention has a plurality of layers containing cyclic olefin resins, the composition may be the same or different. However, from the viewpoint of the stretchability and processability of the performance film, it is preferred to have a B layer when a layer containing a large amount of polypropylene resin and a small amount of cyclic olefin resin is set as a B layer. It should be noted that the B layer may or may not contain a cyclic olefin resin.

[0065] As specific examples of such a scheme, there can be cited a structure having a B layer on one side of the A layer (a 2-layer structure of the A layer / B layer), a structure having a B layer on both sides of the A layer (a 3-layer structure of the B layer / A layer / B layer), and a structure having more than 4 layers of the outermost layer on both surfaces of the film. From the above viewpoint, a 3-layer structure of the B layer / A layer / B layer, a structure having more than 4 layers of the outermost layer on both surfaces of the film, and a 3-layer structure of the B layer / A layer / B layer are more preferred. It should be noted that, in the case of having a plurality of B layers, the composition of the B layer can be the same or different as long as it contains a large amount of polypropylene resin compared to the A layer and has a small content of cyclic olefin resin.

[0066] It should be noted that, in the biaxially oriented polyolefin film of the present invention, Figure 1In the case where the resin corresponding to the matrix (the white part of the symbol 2) contains the resin corresponding to the domain (the black part of the symbol 3), the matrix part and the domain part are considered as one layer. Figure 3 As shown in the embodiment, the white portion represented by symbol 2 and the black portion represented by symbol 3 each form a layer, and when they are arranged alternately, the white portion and the black portion are each regarded as one layer. Figure 3 In the case of the embodiment shown, the A layer may be a layer formed of a cyclic olefin resin and the B layer may be a layer formed of a polypropylene resin. In such an embodiment, since the raw materials do not need to be mixed, pre-mixing is not required. In addition, in such an embodiment, since the cyclic olefin resin and the polypropylene resin are not mixed in one layer, light scattering due to the structural domain is less likely to occur, and as a result, the transparency of the film tends to be higher.

[0067] As the lamination method that can be used in the biaxially oriented polyolefin film of the present invention, for example, there can be cited a feed block method using coextrusion, a multi-manifold method, a static mixer method, a coating method, etc., but from the viewpoint of production efficiency and production cost, a lamination method using coextrusion (such as melt coextrusion) is preferred.

[0068] In the case where the polyolefin film is a laminated structure, from the perspective of controlling film forming properties and surface shape, the upper limit of the ratio of the thickness of the A layer (a layer containing a cyclic olefin resin, but in the case where there are multiple layers containing a cyclic olefin resin, the layer with the largest amount of cyclic olefin resin is used instead, with the mass conversion of the entire layer being 100% by mass) in the total thickness of the polyolefin film is preferably 99%, more preferably 95%, further preferably 90%, and most preferably 85%. In addition, the lower limit is preferably 10%, more preferably 15%, and further preferably 20%. Regarding the ratio of the thickness of the A layer, for example, in the case where the polyolefin film is a three-layer structure of B layer / A layer / B layer in which the B layer is directly laminated on both surfaces of the A layer, the thickness of the A layer other than the thickness of the B layer on both surfaces can be divided by the thickness of the polyolefin film and expressed as a percentage to obtain it. By making the ratio of the A layer 99% or less, the area ratio in stretching can be fully increased, and the mechanical properties can be improved. On the other hand, by making the ratio of the A layer 10% or more, the optical properties and heat resistance can be improved.

[0069] Regarding the lower limit of the content of the cyclic olefin resin in the A layer in the biaxially oriented polyolefin film of the present invention, from the viewpoint of obtaining excellent optical properties and heat resistance, when all the constituent components of the A layer are set to 100% by mass, the lower limit is preferably 5.0% by mass, more preferably 7.5% by mass, further preferably 10% by mass, and particularly preferably 15% by mass. The upper limit of the content of the cyclic olefin resin in the A layer is preferably 100% by mass, more preferably 80% by mass, further preferably 60% by mass, and particularly preferably 40% by mass. It should be noted that the content of the cyclic olefin resin in the A layer being 100% by mass means that the A layer is formed only of the cyclic olefin resin, and such a scheme is preferably mainly having Figure 3 Such a multi-layer laminated structure.

[0070] From the viewpoint of obtaining excellent stretchability, when all the constituent components of the B layer are set to 100% by mass, the content of the polypropylene resin in the B layer of the biaxially oriented polyolefin film of the present invention is preferably 95% by mass or more, more preferably 96% by mass or more, and further preferably 97% by mass or more. The upper limit is preferably 100% by mass, and more preferably 99.9%.

[0071] Next, resins that can be suitably used for the biaxially oriented polyolefin film of the present invention will be described.

[0072] The biaxially oriented polyolefin film of the present invention preferably contains a linear polypropylene resin (hereinafter sometimes referred to as polypropylene resin (A)) as a main component. The main component here means the component with the highest mass % (the component with the largest content) among all the components constituting the biaxially oriented polyolefin film.

[0073] The lower limit of the number average molecular weight (Mn) of the polypropylene resin (A) is preferably 30,000, more preferably 40,000, further preferably 50,000, and particularly preferably 60,000. On the other hand, the upper limit of Mn is preferably 90,000, more preferably 80,000. By having the above characteristics of the polypropylene resin (A), the film-making stability, the mechanical properties and the heat resistance of the film can be improved. In order to make the Mn of the polypropylene resin (A) the above value, it is preferred to use a method for adjusting the hydrogen concentration during polymerization, a method for appropriately selecting a catalyst and / or a co-catalyst, a method for adjusting the composition of each polymerization tank of continuous polymerization and the amount of polymerization, etc. It should be noted that the Mn of the polypropylene resin can be measured using gel permeation chromatography, and the details of the measuring method are shown in the embodiments.

[0074] The meso pentad fraction (mmmm) of the polypropylene resin (A) is preferably 0.940 or more. More preferably 0.950 or more, further preferably 0.978 or more, further preferably 0.981 or more, and most preferably 0.984 or more. The meso pentad fraction is an index of the stereoregularity of the crystalline phase of polypropylene. The higher the value, the higher the crystallinity and melting point, and the more the mechanical properties can be improved. In addition, since it is easy to maintain planarity when heated, it is suitable for use at high temperatures, so it is preferred. There is no particular provision for the upper limit of the meso pentad fraction, but it is set to 0.999 from the viewpoint of feasibility. In order to obtain such a polypropylene resin with high stereoregularity, it is preferred to use a method such as washing the obtained resin powder with a solvent such as n-heptane, a method of appropriately selecting a catalyst and / or a co-catalyst, a method of selecting a composition, etc. It should be noted that the meso pentad fraction of the polypropylene resin can be measured using a nuclear magnetic resonance method (NMR method), and the details of the measuring method are shown in the embodiments.

[0075] The melting point of the polypropylene resin (A) is preferably 160°C or higher. It is more preferably 161°C or higher, further preferably 163°C or higher, particularly preferably 164°C or higher, and most preferably 167°C or higher. The melting point of the polypropylene resin (A) is 160°C or higher, so that the heat resistance can be improved when the film is made. The upper limit of the melting point of the polypropylene resin (A) is not particularly limited, but is 180°C from the perspective of feasibility. In this way, in order to obtain a polypropylene resin with a high melting point, it is preferred to adopt, for example, a method of washing the obtained resin powder with a solvent such as n-heptane, appropriately selecting a catalyst and / or a co-catalyst, and selecting a composition to improve the stereoregularity of the polypropylene resin. In addition, when using a copolymer of propylene, a method of making the copolymerization amount other than propylene less than 1 mol%, etc.

[0076] The melting point of the resin is defined as the melting peak temperature obtained when the resin is heated from 30°C to 260°C at 20°C / min using a differential scanning calorimeter DSC, and the measurement method is described later. In some cases, two or more melting peak temperatures are observed in the above temperature range, and sometimes a multi-stage peak called a shoulder is observed. In such cases, the temperature of the peak with the maximum absolute value of the heat flow (unit: mW) on the vertical axis of the DSC chart is defined as the melting point of the resin.

[0077] The polypropylene resin (A) is preferably mainly composed of a homopolymer of propylene, but a copolymer of propylene containing other unsaturated hydrocarbons as copolymer components may be used within the scope not impairing the purpose of the present invention. Examples of the copolymer components contained in the copolymer of propylene include ethylene, 1-butene, 1-pentene, 3-methylpentene-1, 3-methylbutene-1, 1-hexene, 4-methylpentene-1, 5-ethylhexene-1, 1-octene, 1-decene, 1-dodecene, vinylcyclohexene, styrene, allylbenzene, cyclopentene, norbornene, and 5-methyl-2-norbornene.

[0078] From the viewpoint of heat resistance, the copolymerization amount of components other than propylene in the copolymer of propylene is preferably less than 1 mol%. Here, the copolymerization amount of components other than propylene is less than 1 mol%, which means that when the constituent components of the resin constituting the polypropylene resin (A) are set to 100 mol%, the constituent components other than propylene are less than 1 mol%. That is, when the polypropylene resin (A) is composed of a polypropylene polymer having a copolymerization amount of less than 1 mol%, or when a polypropylene polymer having a copolymerization amount of 1 mol% or more and a homopolymer of propylene (or a polypropylene polymer having a copolymerization amount of less than 1 mol%) are mixed in a manner that the components other than propylene account for less than 1 mol% of the whole, the copolymerization amount of components other than propylene is less than 1 mol%.

[0079] In addition, in the polypropylene resin (A), a polymer having components other than propylene as main constituents may be blended. As main constituents in such a polymer, for example, ethylene, 1-butene, 1-pentene, 3-methylpentene-1, 3-methylbutene-1, 1-hexene, 4-methylpentene-1, 5-ethylhexene-1, 1-octene, 1-decene, 1-dodecene, vinylcyclohexene, styrene, allylbenzene, cyclopentene, etc. may be mentioned. From the perspective of mechanical properties and heat resistance, the blending amount of the polymer having components other than propylene as main constituents is preferably less than 1 part by mass relative to 100 parts by mass of the polypropylene resin (A).

[0080] The polypropylene resin (A) is not particularly limited as long as it satisfies the above-mentioned preferred conditions. For example, F-704NP, F-704NT, ​​F-300SP, F113G, E-100GPL, E-105GM, E-200GP, E-203GP, Y-400GP, and E111G, which are polypropylene resins manufactured by Prime Polymer Co., Ltd., and FLX80H5, FLX80E4, WF836DG3, FS2011DG3, D101, and W101, which are polypropylene resins manufactured by Sumitomo Chemical Co., Ltd., are preferably used.

[0081] The biaxially oriented polyolefin film of the present invention may also include a component having a nucleating agent effect in addition to a linear polypropylene resin (A). As a component having a nucleating agent effect, for example, sorbitol-based nucleating agents, nonitol-based nucleating agents, amide-based nucleating agents, aromatic carboxylic acid metal salts, phosphate metal salts, polypropylene resins with cross-linked structures, branched polypropylene resins, etc. can be cited, but the nucleating agent is preferably a nucleating agent compatible or micro-dispersed in the film, preferably using a branched polypropylene resin, a sorbitol-based nucleating agent known as a melt-type nucleating agent, and a nonitol-based nucleating agent. Among them, from the viewpoint of suppressing the film breakage during production caused by foreign matter, it is preferred to use a branched polypropylene resin.

[0082] Branched polypropylene resin is commercially available in a variety of Ziegler-Natta catalyst systems, metallocene catalyst systems, etc., but from the viewpoint of being used in combination with polypropylene resin (A), it is more preferred to add a small amount of Ziegler-Natta catalyst system branched polypropylene resin with a wide molecular weight distribution to supplement stretchability. When the biaxially oriented polyolefin film includes a branched polypropylene resin, the proportion of the branched polypropylene resin in the entire film is preferably 30% by mass or less, and its upper limit is more preferably 10% by mass, and further preferably 5% by mass. The lower limit is preferably 1% by mass, and more preferably 2% by mass. In the film, when two or more components equivalent to the branched polypropylene resin are included, these components are added together and regarded as the content of the branched polypropylene resin in the film.

[0083] The cyclic olefin resin used for the biaxially oriented polyolefin film of the present invention will be specifically described.

[0084] Examples of the monomer for obtaining the cyclic olefin include monocyclic olefins such as cyclobutene, cyclopentene, cycloheptene, cyclooctene, cyclopentadiene, and 1,3-cyclohexadiene, bicyclo〔2,2,1〕hept-2-ene, 5-methyl-bicyclo〔2,2,1〕hept-2-ene, 5,5-dimethyl-bicyclo〔2,2,1〕hept-2-ene, 5-ethyl-bicyclo〔2,2,1〕hept-2-ene, 5-butyl-bicyclo〔2,2,1〕hept-2-ene, 5-ethyl-bicyclo〔2,2,1〕hept-2-ene, 5-hexyl-bicyclo〔2,2,1〕hept-2-ene, 5-octyl-bicyclo〔2,2,1〕hept-2-ene, 5-octadecyl-bicyclo〔2,2,1〕hept-2-ene, 5-methylene-bicyclo〔2 ,2,1]hept-2-ene, 5-vinyl-bicyclo〔2,2,1〕hept-2-ene, 5-propenyl-bicyclo〔2,2,1〕hept-2-ene, tricyclo〔4,3,0,12.5〕dec-3,7-diene, tricyclo〔4,3,0,12.5〕dec-3-ene, tricyclo〔4,3,0,12.5〕undec-3,7-diene, tricyclo〔4,3,0,12.5〕undec-3,8-diene, tricyclo〔4,3,0,12.5〕undec-3-ene, 5-cyclopentyl-bicyclo〔2,2,1〕hept-2-ene, 5-cyclohexyl-bicyclo〔2,2,1〕hept-2-ene, 5-cyclohexenyl-bicyclo〔2,2,1〕hept-2-ene, 5-phenyl-bicyclo〔 tricyclic olefins such as tetracyclo〔4,4,0,12.5,17.10〕dodec-3-ene, 8-methyltetracyclo〔4,4,0,12.5,17.10〕dodec-3-ene, 8-ethyltetracyclo〔4,4,0,12.5,17.10〕dodec-3-ene, 8-methylenetetracyclo〔4,4,0,12.5,17.10〕dodec-3-ene, 8-ethyltetracyclo〔4,4,0,12.5,17.10〕dodec-3-ene, 8-vinyltetracyclo〔4,4,0,12.5,17.10〕dodec-3-ene, 8-propenyl-tetracyclo〔4,4,0,12.5,17.10〕dodec-3-ene Tetracyclic olefins, and 8-cyclopentyl-tetracyclo〔4,4,0,12.5,17.10〕dodec-3-ene, 8-cyclohexyl-tetracyclo〔4,4,0,12.5,17.10〕dodec-3-ene, 8-cyclohexenyl-tetracyclo〔4,4,0,12.5,17.10〕dodec-3-ene, 8-phenyl-cyclopentyl-tetracyclo〔4,4,0,12.5,17.10〕dodec-3-ene, tetracyclo〔7,4,13.6,01.9,02.7〕tetradec-4,9,11,13-tetraene, tetracyclo〔8,4,14.7,01.10,03.8〕pentadeca-5,10,12,14-tetraene, pentacyclo〔6,6,13.6,02.7,09.14〕-4-hexadecene, pentacyclo〔6,5,1,13.6,02.7,09.13〕-4-pentadecaene, pentacyclo〔7,4,0,02.7,13.6,110.13〕-4-pentadecaene, heptacyclo〔8,7,0,12.9,14.7,111.17,03.8,012.16〕-5-eicosene, heptacyclo〔8,7,0,12.9,03.8,14.7,012.17,113.16〕-14-eicosene, polycyclic olefins such as tetramers such as cyclopentadiene, etc. These cyclic olefin monomers can be used alone or in combination of two or more. .

[0085] As the cyclic olefin monomer, among the above, from the viewpoint of productivity and surface properties, it is preferable to use a tricyclic olefin having 10 carbon atoms such as bicyclo〔2,2,1〕hept-2-ene (hereinafter referred to as norbornene), a tricyclic olefin having 10 carbon atoms such as tricyclo〔4,3,0,12.5〕dec-3-ene (hereinafter referred to as tricyclodecene), a tetracyclic olefin having 12 carbon atoms such as tetracyclo〔4,4,0,12.5,17.10〕dodec-3-ene (hereinafter referred to as tetracyclododecene), cyclopentadiene, or 1,3-cyclohexadiene.

[0086] The cyclic olefin resin may be any of a resin obtained by polymerizing only the above-mentioned cyclic olefin monomer (hereinafter sometimes referred to as COP) and a resin obtained by copolymerizing the above-mentioned cyclic olefin monomer and a chain olefin monomer (hereinafter sometimes referred to as COC), as long as it is a polyolefin resin in which the total amount of components derived from cyclic olefin monomers in 100% by mass of the polymer of the cyclic olefin resin is greater than 10% by mass and is less than 100% by mass.

[0087] As a method for producing COP, known methods such as addition polymerization or ring-opening polymerization of cyclic olefin monomers can be cited, for example, a method of subjecting norbornene, tricyclodecene, tetracyclodecene, and derivatives thereof to ring-opening metathesis polymerization and then hydrogenating the same, a method of subjecting norbornene and derivatives thereof to addition polymerization, a method of subjecting cyclopentadiene and cyclohexadiene to 1,2- or 1,4-addition polymerization and then hydrogenating the same, etc. Among these, a method of subjecting norbornene, tricyclodecene, tetracyclodecene, and derivatives thereof to ring-opening metathesis polymerization and then hydrogenating the same is more preferred from the viewpoint of productivity and moldability. Examples of the COP of the biaxially oriented polyolefin film that can be preferably used in the present invention include “Zeonoa” (registered trademark) 1020R, 1060R, 1410R, 1420R, 1430R, and 1600 manufactured by Zeon Co., Ltd. of Japan, “Zeonex” (registered trademark) 480, 480R, 280R, 490R, E48R, and E28R manufactured by Zeon Co., Ltd. of Japan, and “ARTON” (registered trademark) F3500 and D4000 manufactured by JSR Corporation.

[0088] In the case of COC, preferred chain olefin monomers include ethylene, propylene, 1-butene, 1-pentene, 1-hexene, 3-methyl-1-butene, 3-methyl-1-pentene, 3-ethyl-1-pentene, 4-methyl-1-pentene, 4-methyl-1-hexene, 4,4-dimethyl-1-hexene, 4,4-dimethyl-1-pentene, 4-ethyl-1-hexene, 3-ethyl-1-hexene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-octadecene, 1-eicosene, etc. Among them, ethylene or both ethylene and propylene can be particularly preferably used from the viewpoint of productivity and cost. In addition, as a method for producing a resin obtained by copolymerizing a cyclic olefin monomer and a chain olefin monomer, known methods such as addition polymerization of a cyclic olefin monomer and a chain olefin monomer can be cited, for example, a method of addition polymerization of norbornene and its derivatives with ethylene can be cited, etc. Among them, copolymerization of norbornene with ethylene is more preferred from the viewpoint of productivity and moldability.

[0089] In particular, from the viewpoint of productivity and moldability, as a method for producing COC, a method using binary polymerization or ternary polymerization of norbornene, tetracyclododecene, their derivatives, and ethylene and / or propylene can be used as a preferred method. That is, for example, binary polymerization of a tetracyclododecene derivative and ethylene, and ternary polymerization of norbornene, ethylene, and propylene can be used as a preferred method.

[0090] The linear olefin monomer and the cyclic olefin monomer used to obtain COC may be one kind each, or one or both of them may be two or more kinds. Among them, the use of a cyclic olefin copolymer having ethylene and propylene as structural units is particularly preferred from the viewpoint of improving compatibility with a polypropylene resin. As the cyclic olefin monomer, from the viewpoint of improving the heat resistance of a biaxially oriented polypropylene film, it is preferred to use norbornene, its derivatives, norbornadiene, its derivatives, etc., alone or in combination. As COC that can be preferably used for the biaxially oriented polyolefin film of the present invention, for example, "TOPAS" (registered trademark) 5013F-04, 6013F-04, 6015S-04, 6017S-04 manufactured by Polyplastics, and "APER" (registered trademark) APL6011T, APL6013T, APL6015T, APL5014CL, APL5014DP, APL5014CL(04) manufactured by Mitsui Chemicals, Inc. are mentioned.

[0091] The cyclic olefin resin used in the biaxially oriented polyolefin film of the present invention is preferably amorphous. From the viewpoint of improving the heat resistance when the biaxially oriented polyolefin film is made, the glass transition temperature of the further amorphous cyclic olefin resin is preferably 125°C or more, more preferably 130°C or more, and more preferably 135°C or more. From the viewpoint of co-stretchability with the main component polyolefin resin, the upper limit of the glass transition temperature of the cyclic olefin resin is preferably 180°C, more preferably 175°C, and more preferably 160°C. It should be noted that the glass transition temperature can be measured according to JIS K7121-1987, which will be described in detail later.

[0092] By making the glass transition temperature of the cyclic olefin resin used in the biaxially oriented polyolefin film of the present invention within the above-mentioned preferred range, the heat resistance of the film can be improved. It should be noted that the so-called cyclic olefin resin in the biaxially oriented polyolefin film of the present invention is amorphous, which is defined as the fact that the melting peak temperature (Tm) obtained when the cyclic olefin resin is heated from 30°C to 260°C at 20°C / min using a differential scanning calorimeter DSC is not observed.

[0093] From the viewpoint of improving the optical properties when the film is made, the refractive index of the cyclic olefin resin used in the biaxially oriented polyolefin film of the present invention is preferably 1.510 or more, more preferably 1.520 or more, and further preferably 1.530 or more. The upper limit is not particularly limited, but is substantially 1.600. By making the refractive index of the cyclic olefin resin the above-mentioned preferred range, the optical properties when the film is made can be improved. It should be noted that the so-called refractive index here refers to the refractive index when measured using sodium D rays (wavelength 589nm) as the light source, and the measurement method is described in detail later.

[0094] The biaxially oriented polyolefin film of the present invention may contain various additives such as organic particles, inorganic particles, crystal nucleating agents, antioxidants, heat stabilizers, chlorine scavengers, slip agents, antistatic agents, antiblocking agents, fillers, viscosity modifiers, and coloring inhibitors within the range that does not impair the purpose of the present invention. It should be noted that when the biaxially oriented polyolefin film has a laminated structure, these components may be contained in one layer or in multiple layers.

[0095] Among them, when an antioxidant is contained, the type and amount of the antioxidant are important from the viewpoint of long-term heat resistance. That is, as such an antioxidant, a sterically hindered phenolic substance is used, and at least one of them is preferably a high molecular weight substance with a molecular weight of 500 or more. As specific examples thereof, a variety of substances can be cited, preferably, for example, together with 2,6-di-tert-butyl-p-cresol (BHT: molecular weight 220.4), 1,3,5-trimethyl-2,4,6-tris (3,5-di-tert-butyl-4-hydroxybenzyl) benzene (for example, BASF "Irganox" (registered trademark) 1330: molecular weight 775.2), and tetrakis [methylene-3 (3,5-di-tert-butyl-4-hydroxyphenyl) propionate] methane (for example, BASF "Irganox" (registered trademark) 1010: molecular weight 1,177.7) and the like.

[0096] When the total amount of resin constituting the biaxially oriented polyolefin film is set to 100 parts by mass, the total content of high molecular weight antioxidants with a molecular weight of 500 or more is preferably 0.1 to 1.0 parts by mass. The antioxidant is 0.1 parts by mass or more relative to the total amount of resin constituting the biaxially oriented polyolefin film, thereby improving long-term heat resistance. On the other hand, by being 1.0 parts by mass or less, the blocking at high temperature caused by the seepage of the antioxidant is reduced, and the quality reduction can be suppressed when used as a protective film. When the total amount of resin constituting the biaxially oriented polyolefin film is set to 100 parts by mass, the more preferred total content of the antioxidant is 0.2 to 0.7 parts by mass, and more preferably 0.3 to 0.5 parts by mass. In the case of a laminated structure of more than two layers, the total content of high molecular weight antioxidants with a molecular weight of 500 or more in each layer is 0.3 to 0.5 parts by mass relative to the total amount of resin constituting each layer. It is preferred from the viewpoint of suppressing defects such as fish eyes and improving quality.

[0097] The biaxially oriented polyolefin film of the present invention can include resins other than polypropylene resin (A) and cyclic olefin resins in the range that does not damage the purpose of the present invention. As specific resins, vinyl polymer resins, polyester resins, polyamide resins, polyphenylene sulfide resins, polyimide resins, polycarbonate resins, etc., including various polyolefin resins can be cited, and polymethylpentene, olefin elastomer resins, syndiotactic polystyrene, etc. are particularly preferably exemplified. When the resin component constituting the biaxially oriented polyolefin film is set to 100% by mass as a whole, the content of the resin other than polypropylene resin (A) and cyclic olefin resin is preferably less than 4% by mass, more preferably less than 2% by mass, and further preferably less than 1% by mass. By making the content of the resin other than polypropylene resin (A) and cyclic olefin resin less than 4% by mass, the influence of the domain interface can be suppressed, and the reduction of the optical properties and mechanical properties of the biaxially oriented polyolefin film can be reduced.

[0098] The biaxially oriented polyolefin film of the present invention can be obtained by biaxially stretching, heat treating and relaxing a polyolefin sheet using a raw material capable of obtaining the above-mentioned properties. As a biaxial stretching method, any of the methods of inflation simultaneous biaxial stretching, tenter simultaneous biaxial stretching and tenter sequential biaxial stretching can be used, but among them, in terms of improving the film forming stability, crystalline / amorphous structure, surface properties, especially the stretching ratio of the film, and controlling the mechanical properties and thermal dimensional stability, the tenter sequential biaxial stretching method or the tenter simultaneous biaxial stretching method is preferably used.

[0099] Next, the method for producing a biaxially oriented polyolefin film of the present invention is described. The method for producing a biaxially oriented polyolefin film of the present invention is characterized in that it is a method for producing a biaxially oriented polyolefin film, which sequentially comprises the following steps: a pre-mixing step of compounding a cyclic olefin resin and a polypropylene resin before melt extrusion, a stretching step of stretching an unstretched film in the longitudinal direction and the width direction, and a heat treatment step of subjecting the biaxially stretched film to heat treatment and relaxation treatment, wherein the refractive index of the cyclic olefin resin is 1.510 or more and 1.600 or less, the content of the cyclic olefin resin in the biaxially oriented polyolefin film is 2.0% by mass or more and less than 50% by mass, the meso pentad fraction of the polypropylene resin is 0.940 or more, and in the stretching step, the stretching ratio in the longitudinal direction is 4.0 times or more, and the stretching ratio in the longitudinal direction / the stretching ratio in the width direction is 0.4 to 2.5. It should be noted that the phrase "pre-mixing step, stretching step, and heat treatment step are provided in sequence" means that the above three steps are provided in sequence regardless of whether there are other steps before the pre-mixing step, after the heat treatment step, or between the steps.

[0100] The pre-mixing process of compounding the cyclic olefin resin and the polypropylene resin before melt extrusion is provided for the purpose of improving the dispersibility of each resin in advance before the resins are melted by the extruder. Since the dispersibility of the cyclic olefin resin and the polypropylene resin is improved by the pre-mixing process, the domain of the cyclic olefin resin in the polypropylene resin is smaller and evenly dispersed, and it is easier to achieve the reduction of the value obtained by the phase difference Rth in the thickness direction divided by the film thickness and the improvement of heat resistance brought by the cyclic olefin resin. It should be noted that the mixer used in the pre-mixing process is not particularly limited, but from the viewpoint of good dispersion state and the high transparency of the obtained film, a twin-screw extruder is particularly preferred.

[0101] The method for producing a biaxially oriented polyolefin film of the present invention has a stretching process of stretching an unstretched film in the length direction and the width direction. It is a process for imparting biaxial orientation to the film by stretching in the length direction and the width direction. The method of biaxial stretching can be appropriately selected from the above method. It should be noted that the so-called unstretched film is a film before stretching, which refers to a sheet obtained by forming a molten resin into a sheet and solidifying it on a cooling medium such as a casting drum.

[0102] The method for producing a biaxially oriented polyolefin film of the present invention comprises a heat treatment step of subjecting the biaxially stretched film to heat treatment and relaxation treatment after the stretching step. The so-called heat treatment step here refers to a step of applying 2 to 20% relaxation in the width direction and performing heat treatment at 150° C. or above and 190° C. or below. By having the heat treatment step, the micro voids at the domain interface generated in the stretching step can be reduced or eliminated, thereby improving the transparency of the finally obtained biaxially oriented polyolefin film.

[0103] In the method for manufacturing a biaxially oriented polyolefin film of the present invention, the refractive index of the cyclic olefin resin is 1.510 or more and 1.600 or less. By making the refractive index of the cyclic olefin resin 1.510 or more, the interference color and rainbow color unevenness when the biaxially oriented polyolefin film is made are suppressed. From the above viewpoint, the refractive index of the cyclic olefin resin is preferably 1.520 or more, more preferably 1.530 or more. On the other hand, the upper limit of the refractive index of the cyclic olefin resin is 1.600 in order to make the refractive index difference of the polypropylene resin as the matrix below a certain value. Generally speaking, the cyclic olefin resin is incompatible with the polypropylene resin, so when the two are mixed and the film is made, it is easy to damage the transparency, but by making the refractive index of the cyclic olefin resin the above-mentioned preferred range, the deterioration of the transparency can be reduced, and the film with excellent optical properties can be made. It should be noted that the refractive index of the cyclic olefin resin can be measured according to JIS K7142 (2014) B method, which is described in detail later.

[0104] In the method for manufacturing a biaxially oriented polyolefin film of the present invention, from the viewpoints of optical properties, heat resistance, and ease of stretching of the resulting film, the content of the cyclic olefin resin in the biaxially oriented polyolefin film is 2.0% by mass or more and less than 50% by mass. Here, the so-called "content of cyclic olefin resin in biaxially oriented polyolefin film" is the content of cyclic olefin resin when all resin components of the biaxially oriented polyolefin film are set to 100% by mass. From the above viewpoints, the content of cyclic olefin resin in the biaxially oriented polyolefin film is preferably 5.0% by mass or more, more preferably 7.5% by mass or more, and further preferably 9.0% by mass or more. On the other hand, from the viewpoint of ease of stretching and mechanical strength, the content of cyclic olefin resin in the biaxially oriented polyolefin film is preferably 40% by mass or less, more preferably 30% by mass or less, further preferably 20% by mass or less, and particularly preferably 15% by mass or less.

[0105] In the method for manufacturing a biaxially oriented polyolefin film of the present invention, from the viewpoint of improving the mechanical properties and heat resistance when the film is made, the meso pentad fraction of the polypropylene resin is 0.940 or more. From the above viewpoint, it is preferably 0.950 or more, more preferably 0.978 or more, further preferably 0.981 or more, and particularly preferably 0.984 or more. The meso pentad fraction is an index representing the stereoregularity of the crystalline phase of polypropylene, and the higher the value, the higher the crystallinity and melting point. Therefore, by making the meso pentad fraction of the polypropylene resin high, the mechanical properties when the film is made can be improved, and the adaptability of use at high temperatures is also improved. There is no particular provision for the upper limit of the meso pentad fraction, but it is considered to be 0.999 from the viewpoint of feasibility. In order to obtain such a polypropylene resin with high stereoregularity, it is preferred to adopt a method such as washing the obtained resin powder with a solvent such as n-heptane, a method of appropriately selecting a catalyst and / or a co-catalyst, and a method of selecting a composition. It should be noted that the meso pentad fraction of the polypropylene resin can be measured using a nuclear magnetic resonance method (NMR method), and the details of the measuring method are shown in the examples. In addition, the measurement of the meso pentad fraction in the case where a plurality of components corresponding to the polypropylene resin are mixed can be carried out in a state containing all the polypropylene resins, i.e., without separating the components.

[0106] In the method for producing a biaxially oriented polyolefin film of the present invention, the stretching ratio in the length direction is 4.0 times or more, and the stretching ratio in the length direction / stretching ratio in the width direction (hereinafter, sometimes referred to as the stretching ratio ratio) is 0.4 to 2.5. By setting the stretching ratio in the length direction in this way, the thermal dimensional stability of the obtained biaxially oriented polyolefin film is improved. In addition, by making the ratio of the stretching ratio 0.4 to 2.5, the orientation of the molecular chains in the length direction and the width direction is more isotropic, so that the birefringence in the in-plane direction of the obtained biaxially oriented polyolefin film can be reduced, and the optical properties (for example, quality, visibility, etc.) can be well adjusted. From the above viewpoints, the upper limit of the stretching ratio ratio is preferably 2.5, more preferably 2.0, further preferably 1.5, and particularly preferably 1.2, and the lower limit is preferably 0.4, preferably 0.5, more preferably 0.7, and further preferably 0.8.

[0107] Next, regarding the biaxially oriented polyolefin film of the present invention, a film having a layer containing a cyclic olefin resin and a polypropylene resin (A) is given as an example and its production method is specifically described. However, the biaxially oriented polyolefin film of the present invention is not limited to the one obtained by the following method.

[0108] First, in the pre-mixing step, a cyclic olefin resin and a polypropylene resin (A) are pre-mixed to obtain a composite resin raw material, which is diluted or directly melt-extruded on a support to form an unstretched film. The unstretched film is stretched in the length direction and then stretched in the width direction to perform a successive biaxial stretching. Then, a heat treatment and a relaxation treatment are performed to produce a biaxially oriented polyolefin film. The following is a more specific description, but the present invention is not necessarily limited to this and is interpreted.

[0109] First, for the biaxially oriented polyolefin film of the present invention, from the viewpoint of obtaining high transparency by making the dispersion state of cyclic olefin resin and polypropylene resin (A) good, thereby particularly improving the optical characteristics and heat resistance of the film, preferably in the pre-mixing process, cyclic olefin resin, polypropylene resin (A), and antioxidant are mixed in advance for compounding. Single screw extruder, twin screw extruder etc. can be used for compounding, but from the viewpoint of good dispersion state and high transparency of the obtained film, it is particularly preferred to use a twin screw extruder.

[0110] The amount of the antioxidant is preferably 0.1 parts by mass or more, more preferably 0.2 parts by mass or more, and even more preferably 0.3 parts by mass or more per 100 parts by mass of the composite resin component. From the viewpoint of preventing bleeding, the upper limit is 1.0 parts by mass.

[0111] Then, the resin raw material obtained by compounding the cyclic olefin resin and the polypropylene resin (A) is supplied to a single screw extruder, melted and extruded from a slit-shaped die after passing through a filter. At this time, the melt temperature in the extruder is 260 to 280°C, the temperature of the short tube from the filter to the die is 250 to 270°C, and the temperature of the die lip is 240 to 260°C. Such a step-by-step low temperature is preferably considered from the viewpoint that the structural domain of the cyclic olefin resin can be elongated along the extrusion direction and the thickness of the structural domain can be thin. From the above viewpoint, the extruder temperature is preferably 3 to 15°C higher than the short tube temperature, more preferably 5 to 12°C, further preferably 7 to 12°C, and particularly preferably 8 to 12°C. In addition, from the same viewpoint, the short tube temperature is preferably 3 to 15°C higher than the die lip temperature, more preferably 5 to 12°C, further preferably 7 to 12°C, and particularly preferably 8 to 12°C. Then, the molten sheet extruded from the slit die is solidified on a casting drum (cooling drum) controlled at a temperature of 10 to 110° C., preferably 10 to 85° C., more preferably 10 to 65° C., further preferably 20 to 60° C., and particularly preferably 20 to 40° C. to obtain an unstretched polyolefin film.

[0112] It should be noted that in the stretching process described later, it is preferred to make the unstretched polyolefin film a laminated structure from the viewpoint of further improving the area stretching ratio. In this case, the resin raw material obtained by pre-compounding the cyclic olefin resin and the polypropylene resin (A) is supplied to the single screw extruder for the inner layer (A layer), and the polypropylene resin (A) same as the material used in the A layer is supplied to the single screw extruder for the surface layer (B layer), and the laminated body of the molten resin composed of three layers of B layer / A layer / B layer laminated by the feed block method using melt co-extrusion is extruded from the slit-shaped die as a molten sheet. Then, the molten sheet extruded from the slit-shaped die is solidified on a cooling drum controlled to a temperature of 10 to 110°C, preferably 15 to 85°C, more preferably 15 to 65°C, further preferably 20 to 60°C, and particularly preferably 20 to 40°C to obtain an unstretched polyolefin film.

[0113] As a method for bonding the molten sheet to the casting drum, any of the methods of electrostatic application, bonding using the surface tension of water, air knife method, pressure roll method, underwater casting method, air chamber method, etc. can be used alone or in combination, but it is preferred to use the air knife method that can control the planarity and surface roughness. In addition, when the air knife method is used, in order to prevent the unstretched polyolefin film from vibrating, it is also preferred to appropriately adjust the position of the air knife in such a way that the air flows to the downstream side of the film. In addition, the temperature of the air is preferably 15 to 60°C, and more preferably 30 to 60°C.

[0114] Next, in the stretching process, the unstretched polyolefin film is biaxially stretched to make it biaxially oriented. The biaxial stretching method can be a sequential biaxial stretching method or a simultaneous biaxial stretching method. In the case of using the sequential biaxial stretching method, the unstretched polyolefin film is preferably maintained at a temperature of 100 to 170°C, more preferably maintained at 120 to 165°C and using a longitudinal stretching machine that utilizes the circumferential speed difference of the roller, stretched in the length direction to preferably 4.0 to 12 times, more preferably 4.5 to 11 times, further preferably 5.0 to 10 times, and particularly preferably 5.5 to 10 times, and then cooled to room temperature. By setting the stretching ratio in this way, the thermal dimensional stability is improved, so it is easy to control the heat shrinkage rate of the main orientation direction of the obtained biaxially oriented polyolefin film at 150°C to a suitable range, and as a result, the planarity during heating, which is an indicator of heat resistance, can be improved.

[0115] Here, it is preferred to expand the stretching interval distance between the roller on the low speed side and the roller on the high speed side of the longitudinal stretching machine, and to strongly neck the film to a degree that is not excessive, from the viewpoint that the structural domain of the cyclic olefin resin can be extended along the stretching direction, so that the thickness of the structural domain is thin. Here, the so-called stretching interval distance refers to the interval from the position of the most downstream side where the stretching roller on the upstream side is connected to the film to the position of the most upstream side where the stretching roller on the downstream side is connected to the film. From the above viewpoint, the stretching interval distance is preferably 5 to 30 mm, more preferably 10 to 28 mm, and further preferably 15 to 25 mm.

[0116] In addition, in order to ensure the temperature of the film when the stretching interval distance is expanded, it is preferred to set a radiation heater (RH) above and below the film in the stretching and heat the two sides of the film. By heating in this way, the film can be stretched more evenly, and the shrinkage in the film surface is suppressed. The planarity and optical properties during heating can be improved. The RH output at this time is preferably 1.0~5.0kW when the distance between RH and the film is 100mm, more preferably 2.0~4.0kW, and further preferably 3.0~4.0kW. In addition, the distance between RH and the film is preferably more than 10mm and less than 200mm. It should be noted that when adjusting the distance between RH and the film, the output of RH can be adjusted in a manner that provides the film with the same degree of heat as the above conditions.

[0117] Then, the two ends of the film in the width direction that has been uniaxially stretched in the length direction are gripped with a plurality of clamps and guided into a tenter. In the tenter, preheating for stretching in the width direction is first performed, and the temperature of the preheating process is preferably the stretching temperature in the width direction to the stretching temperature in the width direction + 15°C, and more preferably the stretching temperature in the width direction + 4 to + 12°C. Specifically, the preheating temperature is preferably 160 to 185°C, more preferably 170 to 185°C, and further preferably 175 to 185°C. By using such a preheating temperature condition, the fibril structure that is highly oriented in the length direction by uniaxial stretching can be further enhanced, and the heat resistance of the biaxially oriented polyolefin film finally obtained can be improved. In addition, stabilizing the molecular chains that are not sufficiently oriented after uniaxial stretching by preheating at high temperature is also preferred in terms of improving the heat resistance of the biaxially oriented polyolefin film finally obtained.

[0118] After the preheating is completed, the uniaxially oriented polyolefin film is stretched in the width direction while being held at both ends in the width direction by a clamp. The temperature at this time (stretching temperature in the width direction) is preferably 150 to 185°C, more preferably 166 to 180°C, and further preferably 168 to 180°C. In addition, the stretching ratio in the width direction is preferably 5.0 to 20.0 times, more preferably 6.0 to 15.0 times, further preferably 7.0 to 11.0 times, and particularly preferably 7.5 to 10.0 times. By making the stretching ratio in the width direction the above-mentioned preferred range, the fibril structure highly oriented in the length direction by uniaxial stretching is evenly cracked in the width direction, which can reduce the uneven orientation angle in the main orientation direction and improve the quality of the biaxially oriented polyolefin film finally obtained.

[0119] The upper limit of the ratio of the stretch ratios in the sequential biaxial stretching method or the simultaneous biaxial stretching method, (stretch ratio in the length direction) / (stretch ratio in the width direction), is preferably 2.5, more preferably 2.0, further preferably 1.5, and particularly preferably 1.2, and the lower limit is preferably 0.4, more preferably 0.5, further preferably 0.7, and particularly preferably 0.8. By making the ratio of the stretch ratios in the above preferred range, the orientation of the molecular chains in the length direction and the width direction is more isotropic, so that the birefringence in the in-plane direction of the obtained biaxially oriented polyolefin film can be reduced, and the optical properties can be well adjusted.

[0120] The lower limit of the area stretching ratio is preferably 25.0 times, more preferably 30.0 times, further preferably 35.0 times, particularly preferably 40.0 times, most preferably 45.0 times, and the upper limit is preferably 90.0 times, more preferably 80.0 times, further preferably 70.0 times, and particularly preferably 60.0 times. By making the area stretching ratio more than 25.0 times, the molecular chain tension in the film surface is increased and the domain structure is reduced or thinned, so the optical properties and heat resistance of the film can be combined. In addition, by making the area ratio less than 90.0 times, the orientation of the molecular chain in the in-plane direction can be appropriately suppressed, the birefringence in the thickness direction of the polyolefin film is reduced, and the optical properties are well adjusted. In the present invention, the so-called area stretching ratio is the value obtained by multiplying the stretching ratio in the length direction by the stretching ratio in the width direction.

[0121] In the manufacture of the biaxially oriented polyolefin film of the present invention, heat treatment and relaxation treatment are performed after biaxial stretching (after stretching in the width direction in the case of sequential biaxial stretching) (this process is referred to as a heat treatment process). For the heat treatment process, it is preferred to give 2 to 20% relaxation in the width direction while holding both ends in the width direction with a clamp, and to perform a heat treatment at 150°C or more and 190°C or less from the viewpoint of improving the heat resistance of the film. From the above viewpoints, the heat treatment temperature is more preferably 160°C or more and 185°C or less, and further preferably 170°C or more and 185°C or less. From the above viewpoints, the relaxation treatment rate is more preferably 4 to 18%, further preferably 7 to 15%, and most preferably 9 to 15%. By making the heat treatment after biaxial stretching within the above range, the micro-voids at the domain interface generated during stretching can be reduced or eliminated, thereby improving the transparency of the biaxially oriented polyolefin film finally obtained.

[0122] After the heat treatment and relaxation treatment, the biaxially oriented polyolefin film after the relaxation treatment is guided to the outside of the tenter, and the clamps at both ends in the width direction are released at room temperature. Then, the edge of the film is cut by a winding process, and the obtained biaxially oriented polyolefin film is wound into a product roll. Here, before the biaxially oriented polyolefin film is wound, a corona discharge treatment can be performed in air, nitrogen, carbon dioxide or a mixed gas thereof.

[0123] On the other hand, in the case of adopting the simultaneous biaxial stretching method, the two ends of the unstretched polyolefin film in the width direction are gripped with multiple clamps and guided into the simultaneous biaxial stretching tenter. After the preheating is completed, the unstretched polyolefin film is stretched simultaneously in the length direction and the width direction. The temperature of the preheating process is preferably the stretching temperature to the stretching temperature + 15 ° C, and more preferably the stretching temperature to the stretching temperature ~ + 10 ° C. Specifically, the preheating temperature is preferably 100 to 180 ° C, and more preferably 120 to 175 ° C. In addition, the stretching temperature is preferably 100 to 180 ° C, and more preferably 120 to 170 ° C. The stretching ratio in the length direction and the width direction is preferably 3.0 to 12 times, more preferably 4.0 to 11 times, and further preferably 4.5 to 10 times. By making the stretching temperature and the stretching ratio the above-mentioned preferred range, the molecular orientation in the in-plane direction can be uniform, the orientation angle unevenness in the main orientation direction can be reduced, and the quality of the biaxially oriented polyolefin film finally obtained is improved. It should be noted that, when the simultaneous biaxial stretching method is adopted, the above-mentioned conditions can also be preferably adopted for various conditions in other steps.

[0124] It should be noted that if the main production conditions that are of interest for obtaining the biaxially oriented polyolefin film of the present invention are specifically mentioned, they are as follows as examples. It should be noted that it is preferred that all of these production conditions are satisfied, but it is not necessary to satisfy all of them, and they may be appropriately combined.

[0125] The main component is a polypropylene resin (A) having a number average molecular weight Mn of 30,000 at the lower limit and 90,000 at the upper limit.

[0126] A polypropylene resin (A) having a meso pentad fraction of 0.940 or more is used as a main component.

[0127] · Add a cyclic olefin resin having a glass transition temperature of 125 to 180°C.

[0128] · A cyclic olefin resin having a refractive index of 1.510 to 1.600 is added.

[0129] A composite resin raw material obtained by pre-kneading a cyclic olefin resin and a polypropylene resin is used.

[0130] The content of the cyclic olefin-based resin in the biaxially oriented polyolefin film is 2.0% by mass or more and less than 50% by mass.

[0131] ·The melt extrusion temperature, short tube temperature, and die lip temperature are gradually lowered.

[0132] The stretching ratio in the longitudinal direction is 4.0 times or more.

[0133] When stretching in the longitudinal direction, the film is heated from both sides with radiation heaters, and the stretching interval is expanded to 5 to 30 mm for stretching.

[0134] · (Stretching ratio in the longitudinal direction) / (Stretching ratio in the width direction) is 0.4 to 2.5.

[0135] The preheating temperature during transverse stretching is 4 to 15°C higher than the stretching temperature.

[0136] After biaxial stretching, heat treatment and relaxation treatment are performed.

[0137] The biaxially oriented polyolefin film of the present invention is excellent in heat resistance, mechanical properties and quality, so it can be used as an industrial material film and is suitable for use. The so-called industrial material film here refers to a surface protection film, a process film, a release film, etc. The so-called surface protection film refers to a film that has the function of being attached to objects such as molded bodies and films to prevent scratches and contamination during processing and transportation. The so-called process film refers to a film that is attached to objects such as molded bodies and films to prevent scratches and contamination during manufacturing and processing, and is discarded when used as a final product. The so-called release film refers to a film with high demoulding properties, which can be attached to objects such as molded bodies and films to prevent scratches and contamination during processing and transportation, and is easily peeled off and discarded when used as a final product.

[0138] In the film for industrial materials, due to the inspection adaptability of the object component and the processability at high temperature, it can be particularly suitable for optical purposes. Here, the so-called optical use refers to the use of adjusting the optical properties such as the transmission and reflection of light or the protection and manufacturing of the components (optical components) used for the purpose. In addition, the biaxially oriented polyolefin film of the present invention can also be used suitably as a packaging film, and further can also be used suitably in the purposes such as sanitary products, agricultural products, construction products, medical products. Here, the so-called packaging film refers to the film used for packaging food and various commodities.

[0139] In addition, the biaxially oriented polyolefin film of the present invention can also be used for polarizing plate applications due to its excellent optical properties. The polarizing plate of the present invention uses the biaxially oriented polyolefin film of the present invention, and as a specific example, there is a polarizing plate in which the biaxially oriented polyolefin film of the present invention is laminated on the surface of a member that is limited to allowing polarized light or polarized light to pass in a specific direction in order to protect the member.

[0140] In addition, the biaxially oriented polyolefin film of the present invention has the characteristic of high heat resistance, so it can also be preferably used as a dielectric film for film capacitors used in particular at high temperatures. It should be noted that, when used for the same purpose, it can be a metal film laminated film having a metal film on at least one side of the biaxially oriented polyolefin film, and a film capacitor can be made using it. That is, the metal film laminated film of the present invention has a metal film on at least one side of the biaxially oriented polyolefin film of the present invention, and the film capacitor of the present invention uses the metal film laminated film of the present invention.

[0141] Example

[0142] Hereinafter, the present invention will be described in detail by way of examples. It should be noted that the properties were measured and evaluated by the following methods.

[0143] (1) Film thickness

[0144] The thickness was measured using a thickness micrometer (manufactured by Anritsu Co., Ltd.) The biaxially oriented polyolefin film was sampled into a 10 cm square size, the thickness was measured at 5 points selected at random, and the average of the obtained values ​​was defined as the film thickness (μm).

[0145] (2) Film refractive index

[0146] A sealing liquid (diiodomethane) was dripped onto the main prism, and a film was placed thereon. A sealing liquid (diiodomethane) was dripped onto the film, and a glass plate (refractive index 1.74) was placed thereon. The refractive index n1 in the main orientation direction of the film, the refractive index n2 in the direction orthogonal to the main orientation, and the refractive index n3 in the thickness direction were measured at 25°C using an Abbe refractometer 4T (manufactured by Atago Co., Ltd.) using sodium D rays (wavelength 589 nm) as a light source according to JIS K7142 (2014) A method.

[0147] (3) Retardation Rth in the thickness direction

[0148] The refractive index n1 in the main orientation direction, the refractive index n2 in the direction perpendicular to the main orientation, and the refractive index n3 in the thickness direction measured by the method described in the above item (2) were obtained, and the retardation Rth (nm) in the thickness direction was calculated according to the following formula. The film thickness (μm) used the value calculated in (1).

[0149] The phase difference in the thickness direction Rth (nm) = ((n1+n2) / 2-n3)×film thickness (μm)×1000.

[0150] (4) Thermal shrinkage in the main orientation direction at 150°C

[0151] Regarding the thermal shrinkage of the film, a film cut into a 10 cm square size with the main orientation direction of the film and the main orientation orthogonal direction as each side was heated in an oven heated to 150°C for 15 minutes with both sides sandwiched by 0.1 mm thick paper. The thermal shrinkage (%) in the main orientation direction at 150°C was calculated according to the following formula based on the dimension L0 (cm) of the main orientation direction of the film before heating and the dimension L1 (cm) of the main orientation direction of the film after heating. It should be noted that regarding the size, the length of the line connecting the center positions of the opposite sides of the 10 cm square film is set as the measurement position. The above measurement was performed 5 times at different positions in the same film, and the average value was set as the thermal shrinkage (%) in the main orientation direction at 150°C.

[0152] Thermal shrinkage ratio (%) = [(L0-L1) / L0]×100.

[0153] (5) tanδ (loss tangent)

[0154] A test piece (width 5 mm × length 20 mm) cut out from a biaxially oriented polyolefin film with the measuring direction as the long side was mounted on the chuck portion of the device in an atmosphere of 23°C and low-temperature cooled to -100°C. Tanδ and E" were measured from -100°C to 180°C after the start of heating. The viscoelasticity-temperature curve was drawn by the dynamic viscoelasticity method, and tanδ at each temperature was calculated. The measurement was carried out with n=3, and the average value of the obtained values ​​was set as tanδ in the measuring direction. It should be noted that the measuring device and conditions are as follows.

[0155] · Device: Rheogel-E4000 (manufactured by UBM)

[0156] Geometry: Stretch

[0157] Distance between chucks: 10mm

[0158] Frequency: 10Hz

[0159] Strain: 0.1~0.2%

[0160] Temperature range: -100~180℃

[0161] Heating rate: 5℃ / min

[0162] ·Measurement atmosphere: Nitrogen.

[0163] (6) In-plane phase difference Re

[0164] The measurement was performed using a phase difference measuring device (KOBRA-21ADH manufactured by Oji Instruments Co., Ltd.). The biaxially oriented polyolefin film was sampled into a 3.5 cm square size and placed in the device so that the main orientation direction of the film was at an angle of 0° defined in this measuring device. Then, the phase difference Re (nm) in the in-plane direction at a wavelength of 590 nm was measured.

[0165] (7) Dynamic friction coefficient μd

[0166] The biaxially oriented polyolefin film was cut into two pieces with a width of 6.5 cm (film main orientation direction) and a length of 12 cm (film main orientation orthogonal direction) to prepare a test piece. The dynamic friction coefficient (μd) of the test piece in the main orientation orthogonal direction was measured at 25°C and 65% RH using a sliding tester manufactured by Toyo Seiki Co., Ltd. in accordance with JIS K 7125 (1999). It should be noted that the measurement was performed in such a way that the main orientation orthogonal directions overlapped with each other and different surfaces of the film were in contact with each other. The same measurement was performed 5 times on a sample, and the average value of the obtained values ​​was calculated and set as the dynamic friction coefficient (μd) of the sample.

[0167] (8) Product of puncture strength and thickness

[0168] The test piece (width 80mm × length 80mm) cut out of the biaxially oriented polyolefin film was placed on the stage of the KES-G5 handy compression tester manufactured by Katotech Co., Ltd. without loosening. A needle with a front end R of 1mm was used to puncture at a speed of 2mm / sec, and the load (gf) when the needle penetrated was read and multiplied by the film thickness of the sample to calculate the product of the puncture strength and the thickness (gf·μm). The measurement was performed 5 times for each sample, and the average value was evaluated. It should be noted that the film thickness used to calculate the product of the puncture strength and the thickness used the value measured in (1) above.

[0169] (9) Young's modulus at room temperature and specific orientation direction

[0170] A rectangular sample of 150 mm in length (measurement direction) × 10 mm in width was cut from the biaxially oriented polyolefin film. Then, the sample was placed in a tensile testing machine (Orientec "Tensilon" (registered trademark) UCT-100) with an initial chuck distance of 50 mm, and the tensile test of the film was performed at room temperature with a tensile speed of 300 mm / min. Then, the tensile strength and Young's modulus were calculated according to the method specified in JIS K7161 (2014). The measurement was performed 5 times for each sample, and the average value was set as the tensile strength and Young's modulus of the sample. The width direction was set to 0°, and the Young's modulus was measured in the same manner in each direction at an angle of 0° to 175° at 5° intervals relative to the width direction, and the direction showing the highest value was set as the main orientation direction.

[0171] (10) Meso pentad fraction of polypropylene resin (mmmm)

[0172] The polypropylene resin was frozen and crushed into powder, extracted with n-heptane at 60°C for 2 hours, and after removing impurities and additives in the polypropylene, it was dried under reduced pressure at 130°C for more than 2 hours to prepare a sample. The sample was dissolved in a solvent and 13 The meso pentad fraction (mmmm) was determined by C-NMR under the following conditions.

[0173] Measurement conditions

[0174] · Equipment: DRX-500 manufactured by Bruker

[0175] Determination of core: 13 C core (resonance frequency: 125.8MHz)

[0176] ·Measurement concentration: 10% by mass

[0177] Solvent: Benzene: deuterated o-dichlorobenzene = 1:3 mixed solution (volume ratio)

[0178] ·Measurement temperature: 130℃

[0179] Rotation speed: 12Hz

[0180] NMR sample tube: 5mm tube

[0181] Pulse width: 45° (4.5μs)

[0182] Pulse repetition time: 10 seconds

[0183] Data points: 64K

[0184] Cumulative times: 10,000 times

[0185] Measurement mode: complete decoupling

[0186] Parsing conditions

[0187] Fourier transform was performed with LB (line broadening factor) set to 1, and the mmmm peak was set to 21.86ppm. Peak segmentation was performed using WINFIT software (Bruker system). At this time, peak segmentation was performed as follows from the peak on the high magnetic field side, and the automatic fitting of the software was further performed. After the optimization of peak segmentation, the total peak fraction of mmmm was set to the meso pentad fraction (mmmm).

[0188] (a) mrrm

[0189] (b)(c)rrrm (divided into 2 peaks)

[0190] (d)rrrr

[0191] (e)mrmr

[0192] (f)mrmm+rmrr

[0193] (g)mmrr

[0194] (h)rmmr

[0195] (i)mmmr

[0196] (j)mmmm

[0197] The same measurement was performed five times on the same sample, and the average value of the obtained meso pentad fractions was defined as the meso pentad fraction of the sample.

[0198] (11) Melting peak temperature of resin (Tm)

[0199] Using a differential scanning calorimeter (Thermoplus EVO2 DSCvesta manufactured by Rigaku), 3 mg of the resin was heated from 30°C to 260°C at 20°C / min in a nitrogen atmosphere (first heating), then kept at 260°C for 5 minutes, cooled to 30°C at 20°C / min, and then heated again from 30°C to 260°C at 20°C / min (second heating). The endothermic peak temperature obtained during the second heating process was defined as the melting peak temperature (melting point, Tm) of the resin. In this example, Tm was calculated from the average value of n=3 measurements. Sometimes, two or more peak temperatures are observed in the range of more than 170°C and less than 200°C, and sometimes a peak temperature observable in a multi-stage DSC graph called a shoulder peak (observed in the case of a graph with two or more peaks overlapping). However, in this embodiment, the temperature of the peak with the largest absolute value of the heat flow (unit: mW) on the vertical axis of the DSC graph is set to Tm (°C).

[0200] (12) Glass transition temperature (Tg) of cyclic olefin resin

[0201] The measurement was performed in accordance with JIS K7121-1987. Using a differential scanning calorimeter (EXSTAR DSC6220 manufactured by Seiko Instruments), 3 mg of the resin was heated from 30°C to 260°C at 20°C / min in a nitrogen atmosphere, then kept at 260°C for 5 minutes and then cooled to 30°C at 20°C / min. Further, after being kept at 20°C for 5 minutes, the temperature was raised from 30°C to 260°C at 20°C / min as a re-heating. The glass transition temperature (Tg) was calculated from the DSC curve obtained during the re-heating process by the following formula.

[0202] Glass transition temperature = (extrapolated glass transition start temperature + extrapolated glass transition end temperature) / 2.

[0203] (13) Refractive Index of Cyclic Olefin Resin

[0204] The refractive index of the cyclic olefin resin was measured at 25° C. using an Abbe refractometer 4T (manufactured by Atago Co., Ltd.) using sodium D rays (wavelength 589 nm) as a light source and diiodomethane as a sealing liquid according to JIS K7142 (2014) B method.

[0205] (14) Number average molecular weight of polypropylene resin (Mn)

[0206] 1,2,4-trichlorobenzene was used as a solvent and stirred at 165°C for 30 minutes to dissolve the polypropylene resin. Then, the mixture was filtered using a 0.5 μm filter and the molecular weight distribution of the filtrate was determined by gel permeation chromatography. The molecular weight was corrected using a molecular weight standard curve prepared using the following standard samples to obtain the number average molecular weight Mn of the sample. It should be noted that the measuring device and conditions are as follows.

[0207] · Equipment: Agilent high temperature GPC equipment PL-GPC220

[0208] Detector: Agilent differential refractive index detector (RI detector)

[0209] Column: Agilent PL1110-6200 (20 μm MIXED-A) × 2

[0210] Flow rate: 1.0mL / min

[0211] Column temperature: 145°C

[0212] Injection volume: 0.500mL

[0213] Sample concentration: 0.1wt%

[0214] · Standard sample: Monodisperse polystyrene manufactured by Tosoh, bibenzyl manufactured by Tokyo Chemical Industry.

[0215] (15) Melt tension of polypropylene resin

[0216] The measurement was performed under the following conditions using an apparatus in accordance with JIS K 7199 (1999).

[0217] · Equipment: Capilograph 1BPMD-i with melt tension tester (manufactured by Toyo Seiki Co., Ltd.)

[0218] Temperature: 230℃ (used in insulation room)

[0219] Die head: L = 8 (mm), D = 2.095 (mm)

[0220] Extrusion speed: 20mm / min

[0221] ·Traction speed: 15.7m / min

[0222] Sample mass: 15-20 g.

[0223] (16) Number of interfaces per 1 μm in the thickness direction

[0224] Using the sectioning method, ultrathin sections with cross sections along the thickness direction orthogonal to the main orientation of the polyolefin film were obtained. The obtained sections were stained with RuO4 and the cross sections were observed using a transmission electron microscope (TEM) under the following conditions. It should be noted that at this time, the cyclic olefin resin was relatively stained black compared to the polypropylene resin.

[0225] · Equipment: Transmission electron microscope (TEM) HT7700 manufactured by Hitachi, Ltd.

[0226] Accelerating voltage: 100 kV

[0227] Observation magnification: 2,000 times

[0228] After binarization of the image obtained by the above observation, the number of interfaces per 1 μm thickness was determined according to the following steps. Along a 1 μm line segment parallel to the thickness direction, the white portion (non-dyed portion) was set to 0 and the black portion (dyed portion) was set to 1, and a graph was plotted relative to the length in the thickness direction, and the sum of the number of times switching from 0 to 1 and the number of times switching from 1 to 0 was set as the number of interfaces per 1 μm thickness direction.

[0229] (17) Maximum cross-sectional height St

[0230] The maximum cross-sectional height St was measured using a scanning white interference microscope VS1540 manufactured by Hitachi HiTech Science, a three-dimensional non-contact surface shape measuring instrument. In addition, during the analysis, the captured image was corrected using a polynomial quadratic approximation surface by the attached analysis software to remove the undulating components, and then processed using a median (3×3) filter, followed by interpolation processing (processing of supplementing pixels for which height data could not be obtained with height data calculated from surrounding pixels). The measurement conditions are as follows.

[0231] Manufacturer: Hitachi High-tech Co., Ltd.

[0232] Device name: Scanning white interference microscope VS1540

[0233] ·Measurement conditions: Objective lens 10×

[0234] Lens tube 1×

[0235] Variable focal length lens 1×

[0236] Wavelength filter 530nm white

[0237] ·Measurement mode: Wavelength

[0238] Measurement software: VS-Measure Version 10.0.4.0

[0239] Analysis software: VS-Viewer Version10.0.3.0

[0240] ·Measurement area: 0.561×0.561mm 2 .

[0241] (18) Planarity during heating

[0242] The surface with a low value of the maximum cross-sectional height St of the biaxially oriented polyolefin film of 500mm width was subjected to corona treatment. After the acrylic emulsion adhesive (made by I-Tech, EX243) was applied to the treated surface, it was led to a drying oven at 130°C and conveyed for 60 seconds with a conveying tension of 200N. The solvent in the coating agent was removed to obtain a film with an adhesive layer thickness of 1μm. Then, the adhesive film was wound into a roll with a roll length of 200m to make an adhesive film roll. Next, the adhesive film of 500mm width was unrolled for only 1m, without adding tension (a state of hanging down in a vertical direction by the dead weight of the film), without unevenly adding 1kg / m of tension uniformly to the entire width of the film, and without unevenly adding 3kg / m of tension uniformly to the entire width of the film, and the presence or absence of poor planarity positions such as wrinkles and pits was visually confirmed. The obtained value was used to evaluate planarity by the following benchmarks. It should be noted that St used the value measured in the above (17).

[0243] S: There is no position with poor planarity when there is no tension.

[0244] A: Although the location of poor flatness was observed when there was no tension, the location of poor flatness disappeared when the tension was 1 kg / m width.

[0245] B: Although the position of poor planarity was observed at a tension of 1 kg / m width, the position of poor planarity disappeared at a tension of 3 kg / m width, and there was no problem in practical use.

[0246] C: Even at a tension of 3 kg / m width, a location with poor planarity was observed.

[0247] (19) Visualization test

[0248] A test piece was prepared by attaching a sample cut from the center of the film in the width direction to a size of 420 mm in the width direction and 310 mm in the length direction to one surface of a polarizing plate with a polarization degree of 99.9% produced by adsorbing and orienting iodine in polyvinyl alcohol (PVA). The prepared test piece was overlapped with a polarizing plate without a film in a crossnicol configuration, and the visibility was confirmed when placed on a white LED light source (A3-101 manufactured by Tritech).

[0249] S: Little light leakage, and almost no interference color is observed.

[0250] A: Although there is light leakage, interference color is hardly observed.

[0251] B: Although some interference colors were observed, there was no problem in practical use.

[0252] C: Interference colors are clearly observed.

[0253] (Polypropylene resin, etc.)

[0254] In the manufacture of the polyolefin films of the Examples and Comparative Examples, polypropylene resins having the meso pentad fraction, melting point, and Mn shown in the following Table 1 were used. These values ​​are values ​​evaluated in the form of resin particles. In addition, the following materials were used as branched polypropylene resins, cyclic olefin resins, and other raw materials. In some Examples and some Comparative Examples, materials prepared in advance as described below were used as raw materials for the manufacture of polypropylene films.

[0255] <Polypropylene resin>

[0256] Polypropylene Resin 1 (PP1): (manufactured by Polymer Co., Ltd.)

[0257] Polypropylene Resin 2 (PP2): (manufactured by Polymer Co., Ltd.)

[0258] Polypropylene Resin 3 (PP3): (manufactured by Polymer Co., Ltd.)

[0259] Polypropylene resin 4 (PP4): FLX80H5 manufactured by Sumitomo Chemical Co., Ltd.

[0260] [Table 1]

[0261]

Table 1

[0262]

[0263] <Branched polypropylene resin>

[0264] Branched polypropylene resin 1 (branched PP1): Ziegler-Natta catalyst-based branched polypropylene resin (PF-814, manufactured by Basell, melt tension: 15 gf).

[0265] <Cyclic olefin resin>

[0266] Cyclic olefin resin 1 (COC1): TOPAS (registered trademark) 6013F-04 manufactured by Polyplastics (resin obtained by copolymerizing ethylene and norbornene). Glass transition temperature: 138° C., refractive index: 1.533

[0267] Cyclic olefin resin 2 (COC2): Appel APL5014CL (04) manufactured by Mitsui Chemicals, Inc. Glass transition temperature: 135° C., refractive index: 1.544

[0268] Cyclic olefin resin 3 (COP3): Zeonoa 1420R manufactured by Zeon Corporation of Japan. Glass transition temperature: 136° C., refractive index: 1.530.

[0269] It should be noted that when the melting peak temperature (melting point, Tm) of these cyclic olefin resins was measured by the method described in (11), Tm was not observed in any of them, indicating that they were amorphous.

[0270] <Other ingredients>

[0271] 4-Methyl-1-pentene polymer 1: MX004 manufactured by Mitsui Chemicals, Inc.

[0272] Antioxidant: "Irganox" (registered trademark) 1010 manufactured by BASF.

[0273] <Polyolefin raw materials>

[0274] Polyolefin raw material 1: 66 parts by mass of polypropylene resin 1, 34 parts by mass of cyclic olefin resin 1 and 0.5 parts by mass of antioxidant were supplied from a metering hopper to a twin-screw extruder, melt-kneaded at 260° C., and the molten resin composition was discharged from a die in the form of strips, cooled and solidified in a water tank at 25° C., and cut into thin sheets.

[0275] Polyolefin raw material 2: 82 parts by mass of polypropylene resin 2, 5 parts by mass of branched polypropylene resin 1, 13 parts by mass of cyclic olefin resin 2 and 0.5 parts by mass of antioxidant were supplied from a measuring hopper to a twin-screw extruder, melt-kneaded at 260° C., and the molten resin composition was discharged from a die in the form of strips, cooled and solidified in a water tank at 25° C., and cut into sheets.

[0276] Polyolefin raw material 3: 38 parts by mass of polypropylene resin 2, 50 parts by mass of polypropylene resin 3, 3 parts by mass of branched polypropylene resin 1, 9 parts by mass of cyclic olefin resin 2 and 0.5 parts by mass of antioxidant were supplied from a measuring hopper to a twin-screw extruder, melt-kneaded at 260° C., and the molten resin composition was discharged from a die in a strip shape, cooled and solidified in a water tank at 25° C., and cut into a sheet-like material.

[0277] Polyolefin raw material 4: 90 parts by mass of polypropylene resin 1, 10 parts by mass of 4-methyl-1-pentene polymer 1 and 0.5 parts by mass of antioxidant were supplied from a metering hopper to a twin-screw extruder, melt-kneaded at 260° C., and the molten resin composition was discharged from a die in the form of strips, cooled and solidified in a water tank at 25° C., and cut into thin sheets.

[0278] Polyolefin raw material 5: 80 parts by mass of polypropylene resin 2, 20 parts by mass of branched polypropylene resin 1 and 0.5 parts by mass of antioxidant were supplied from a metering hopper to a twin-screw extruder, melt-kneaded at 260° C., and the molten resin composition was discharged from a die in the form of strips, cooled and solidified in a water tank at 25° C., and cut into thin sheets.

[0279] Polyolefin raw material 6: 89.8 parts by mass of polypropylene resin 1, 10.2 parts by mass of cyclic olefin resin 3 and 0.5 parts by mass of antioxidant were supplied from a metering hopper to a twin-screw extruder, melt-kneaded at 260° C., and the molten resin composition was discharged from a die in the form of strips, cooled and solidified in a water tank at 25° C., and cut into thin sheets.

[0280] Polyolefin raw material 7: 70 parts by mass of polypropylene resin 2, 30 parts by mass of cyclic olefin resin 3 and 0.5 parts by mass of antioxidant were supplied from a metering hopper to a twin-screw extruder, melt-kneaded at 265° C., and the molten resin composition was discharged from a die in the form of strips, cooled and solidified in a water tank at 25° C., and cut into thin sheets.

[0281] (Example 1)

[0282] The polypropylene resin 1 and the polyolefin raw material 1 were dry-blended at 50:50 (mass ratio) and supplied to a single-screw extruder for the base layer (A layer). The polypropylene resin 1 and the polyolefin raw material 4 were dry-blended at 70:30 (mass ratio) and supplied to a single-screw extruder for the surface layer (B layer). Each resin mixture was melt-extruded at a melt extrusion temperature of 265°C, a short tube temperature of 255°C, and a die lip temperature of 245°C. After removing foreign matter with a sintered filter with a cutoff of 20μm, the mixture was laminated with a thickness ratio of 1 / 10 / 1 for the surface layer (B layer) / base layer (A layer) / surface layer (B layer) using a feed block type B / A / B composite T-die, and discharged to a casting drum whose surface temperature was controlled to 30°C, and an air knife was used to make it close to the casting drum and cooled and solidified to obtain an unstretched sheet. At this time, the air temperature of the air knife was set to 30°C. Next, the unstretched sheet was preheated to 150°C with a ceramic roller, and between rollers at 150°C with a peripheral speed difference, a radiation heater (RH) was set at a distance of 100mm from the film to heat both sides and stretch 6.2 times in the longitudinal direction to obtain a uniaxially stretched film. At this time, the longitudinal stretching interval distance was set to 20mm, and the RH output was set to 3.5kW. Next, the obtained uniaxially stretched film was introduced into a tenter-type stretching machine while holding both ends in the width direction with clamps, and after preheating at 180°C, it was stretched to 7.5 times in the width direction at 168°C, and heat-treated at 178°C while giving 12% relaxation in the width direction. Then, after a cooling process of 100°C, it was guided to the outside of the tenter, the clamps at both ends of the film in the width direction were released, and it was wound on the core to obtain a biaxially oriented polyolefin film with a thickness of 25μm. The physical properties and evaluation results of the obtained film are shown in Table 2-1.

[0283] (Examples 2 to 7, Comparative Examples 1 to 6)

[0284] The composition and film-making conditions of each layer were as shown in Tables 2-1 and 2-2, and a polyolefin film was obtained in the same manner as in Example 1. At this time, the thickness was adjusted by adjusting the discharge amount during extrusion and adjusting the speed of the casting drum. The physical properties and evaluation results of the obtained films are shown in Tables 2-1 and 2-2. It should be noted that, regarding the raw materials, in the A layer of Example 2, polyolefin raw material 2 was used, and in the B layer of Example 2, polyolefin raw material 5 and polypropylene resin 2 were dry-blended at 20:80 (mass ratio) and used. In the A layer of Example 4, polyolefin raw material 6 was used. In the A layer of Example 5, polyolefin raw material 3 was used, and in the B layer of Example 5, polypropylene resin 1 and polyolefin raw material 4 were dry-blended at 60:40 (mass ratio) and used. In the A layer of Example 7, polyolefin raw material 7 was used. In addition, regarding Comparative Examples 5 and 6, polyolefin films could not be obtained due to film breakage, and various measurements on polyolefin films were not implemented. In Example 3, the laminated structure was formed by alternately laminating the melted cyclic olefin resin 1 (A layer) and the melted polypropylene resin 3 (B layer) using a 201-layer alternate lamination feed block so that the outermost layers on both sides became B layers. At this time, the thickness ratio of each layer was set to 1:1, and only the outermost layers on both sides were set to 3 times the thickness of the other layers (the thickness of each layer was adjusted by adjusting the slit width of the feed block.).

[0285] [Table 2-1]

[0286]

[0287] In the table, the components of each layer are described with the entire resin being 100% by mass, regardless of the amount of the antioxidant. The same applies to Table 2-2 below.

[0288] [Table 2-2]

[0289]

[0290] Industrial Availability

[0291] As described above, the biaxially oriented polyolefin film of the present invention can be used in various industrial applications such as packaging films, surface protection films, process films, sanitary products, agricultural products, construction products, medical products, capacitor films, etc., and is particularly preferably used as a surface protection film, process film, release film, or packaging film for optical components such as polarizing plates due to its excellent optical properties, heat resistance, mechanical strength, and quality.

[0292] Explanation of symbols

[0293] 1: Part of section X

[0294] 2: White part (non-dyed part)

[0295] 3: Black part (dyed part)

[0296] 4: Line segment with a length of 1 μm parallel to the thickness direction

[0297] 5: The white part is set to 0, the black part is set to 1, and the graph is plotted relative to the length in the thickness direction.

Claims

1. A biaxially oriented polyolefin film, wherein the value obtained by dividing the phase difference Rth in the thickness direction by the film thickness is greater than 1.0 and less than 16.0, the heat shrinkage rate in the main orientation direction at 150°C is greater than -5.0% and less than 6.0%, and the film contains a cyclic olefin resin, the unit of the phase difference Rth is nm, and the unit of the film thickness is μm. 2 . The biaxially oriented polyolefin film according to claim 1 , wherein in a cross section of a direction perpendicular to the main orientation and a thickness direction, there is a position where the number of interfaces per 1 μm in the thickness direction is 3 or more and 1000 or less. 3 . The biaxially oriented polyolefin film according to claim 1 , wherein tan δ at 150° C. is 0.01 or more and 0.23 or less in the main orientation direction and the direction perpendicular to the main orientation direction. 4 . The biaxially oriented polyolefin film according to claim 1 , wherein the refractive index in a direction perpendicular to the main orientation is 1.498 or more and 1.550 or less. The biaxially oriented polyolefin film according to any one of claims 1 to 4, wherein a value obtained by dividing an in-plane retardation Re by a film thickness is 0.1 or more and 20.0 or less, the retardation Re being expressed in nm and the film thickness being expressed in μm. 6 . The biaxially oriented polyolefin film according to claim 1 , wherein the dynamic friction coefficient μd in a direction perpendicular to the main orientation is 0.10 or more and 0.70 or less. 7 . The biaxially oriented polyolefin film according to claim 1 , wherein the product of the puncture strength and the thickness is 200 gf·μm or more and 5000 gf·μm or less. 8 . The biaxially oriented polyolefin film according to claim 1 , comprising a polypropylene resin having a number average molecular weight Mn of 30,000 to 90,000 as a main component. 9 . The biaxially oriented polyolefin film according to claim 1 , which is used as an industrial material film.

10. The biaxially oriented polyolefin film according to claim 9, which is used for optical applications. 11 . A polarizing plate using the biaxially oriented polyolefin film according to claim 1 .

12. A metal film laminate film, wherein: The polypropylene film according to any one of claims 1 to 8 has a metal film on at least one surface thereof. 13 . A thin film capacitor using the metal film stacked film according to claim 12 .

14. A method for producing a biaxially oriented polyolefin film, characterized in that: The method comprises the following steps in sequence: a pre-mixing step of compounding a cyclic olefin resin and a polypropylene resin before melt extrusion; a stretching step of stretching an unstretched film in the longitudinal direction and the width direction; and a heat treatment step of heat-treating and relaxing the biaxially stretched film. The refractive index of the cyclic olefin resin is 1.520 or more and 1.600 or less, the content of the cyclic olefin resin in the biaxially oriented polyolefin film is 2.0 mass % or more and less than 50 mass %, and the meso pentad fraction of the polypropylene resin is 0.940 or more, In the stretching step, the stretching ratio in the longitudinal direction is 4.0 times or more, and the ratio of the stretching ratio in the longitudinal direction to the stretching ratio in the width direction is 0.4 to 2.

5.

15. According to the method for producing a biaxially oriented polyolefin film according to claim 14, the value obtained by dividing the phase difference Rth in the thickness direction of the biaxially oriented polyolefin film by the film thickness is greater than 1.0 and less than 16.0, and the thermal shrinkage rate in the main orientation direction at 150°C is greater than -5.0% and less than 6.0%, the unit of the phase difference Rth is nm, and the unit of the film thickness is μm.

Citation Information

Patent Citations

  • Polyolefin film containing cycloolefin polymer and its preparation and use

    JP1997272188A

  • Olefinic laminated film and film capacitor

    JP2018034510A

  • Polyolefin film and its use

    JP2020521867A